Process for producing polyolefin compositions containing recycled polyolefins

JP2026169230APending Publication Date: 2026-10-16SYNSOMER ADHESIVE TECH LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026173496
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-18
Filing Date
2026-07-16
Publication Date
2026-10-16

Smart Images

  • Figure 2026169230000001_ABST
    Figure 2026169230000001_ABST
Patent Text Reader

Abstract

To provide a polyolefin composition containing recycled polyolefins that has a good balance of viscosity, rigidity, and impact strength. [Solution] A process for producing a polyolefin composition, comprising melt-blending (A) at least one recycled polyolefin in about 60 to about 96% by weight, B) at least one random alpha-olefin copolymer in about 2 to about 20% by weight, C) at least one tackifier in about 2 to about 20% by weight, and D) at least one additional polymer optionally, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, and the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer, tackifier, and optional additional polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a polyolefin composition comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, and C) about 2 to about 20% by weight of at least one tackifier, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, and the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier. The present invention also relates to a process for producing a polyolefin composition and an article comprising a polyolefin composition. [Background technology]

[0002] Polyolefins, particularly polyethylene and polypropylene, are being consumed in increasingly large quantities in a wide range of applications, including packaging for food and other goods, textiles, automotive parts, containers, and a diverse array of manufactured products.

[0003] Over the past decade, concerns have arisen regarding the environmental sustainability of plastics and their current use. This has led to the enactment of new legislation concerning the disposal, collection, and recycling of polyolefin materials. In addition, several countries are making efforts to increase the percentage of plastic materials that are recycled instead of sent to landfills.

[0004] Therefore, the use of recycled materials derived from a wide variety of post-consumer and post-industrial sources is increasingly necessary in the field of polyolefins. However, commonly available recycled streams have limited rheological and mechanical properties, reducing their commercially attractive end uses. Currently available flowability and impact modifiers available to upgrade recycled streams tend to be too expensive, making recycling uneconomical, or causing imbalances in rheological and mechanical properties, for example, sacrificing impact strength for yield strength, or sacrificing Young's modulus or viscosity for impact strength.

[0005] In particular, mechanically recycled polymers often exhibit deficiencies in flow properties (low MFI, high viscosity) and impact properties (reduced Izod or Charpy impact strength with and without notches) induced by the recycling process (extrusion) and the use of the pre-recycling material (e.g., exposure to UV, heat, etc.). Currently available commercial solutions often focus on improving a single property (e.g., improving flowability only, or improving impact strength only), and there is a need for an integrated, easy-to-use solution that simultaneously optimizes and balances multiple properties to create a desirable combination with good processability and desirable end-use properties.

[0006] Simultaneous optimization of fluidity and impact strength can also be beneficial for certain unused polyolefins, such as polypropylene homopolymers, providing consumers with more purchasing power if they can adjust lower-impact polypropylene homopolymers to higher impact grades. Similarly, unused polypropylene and polyethylene copolymers can also benefit from the simultaneous optimization and balance of their properties.

[0007] In blends primarily containing polyethylene and polypropylene, higher impact strength can be achieved by adding elastomers that act as compatibilizers, such as conventional ethylene-propylene rubber or EPDM. However, such additions limit the rigidity of the resulting composition.

[0008] More recently developed highly crystalline metallocene-based polypropylene-ethylene elastomers (e.g., Vistamaxx® 6102 from ExxonMobil Chemical Company, Houston, TX, USA) increase impact strength by acting as a compatibilizer between the polyethylene and polypropylene fractions in recycled compounds. However, these solutions still exhibit a decrease in stiffness and yield strength, resulting in only a moderate improvement in rheology.

[0009] The literature suggests the incorporation of heterophasic ethylene-propylene copolymers (HECOs), including ethylene-octene copolymers, which are commercially available from Borealis Plastomers (NL) under the trade name Queo®, The Dow Chemical Company (Midland, MI, USA) under the trade name Engage®, or from ENI SpA (IT). However, the use of any heterophasic ethylene-propylene copolymer (HECO) yields unsatisfactory results, particularly with respect to rigidity.

[0010] It is generally believed that limited stiffness can only be overcome by using plastomers having a block copolymer structure, such as those provided by Dow Chemical INFUSE® olefin block copolymers (OBCs) or INTUNE® OBC plastomers. For example, INTUNE® polypropylene-based OBCs (PP-OBCs) have been introduced as compatibilizers rather than elastomers. They contain propylene-rich blocks compatible with polypropylene and ethylene-rich blocks compatible with polyethylene. It is easy to understand the introduction of the option of block copolymers having certain highly crystalline domains with higher stiffness, thereby increasing overall stiffness. However, plastomers with block copolymer properties have the disadvantage of being relatively expensive.

[0011] Combinations of polyethylene elastomers (e.g., Vistamaxx™ elastomers) and propylene plastomers (e.g., Engage™ ethylene-octen copolymers), as proposed in the literature, are limited by the economic feasibility of the proposed solutions and focus on improving impact strength at the expense of modulus and significant viscosity optimization.

[0012] The literature also suggests incorporating a C2C8 plastomer with a melt flow rate (MFR) of 1.5 g / 10 min or less (ISO1133, 190°C, 2.16 kg) as a more economical solution than using an elastomer in combination with a plastomer. This solution can increase impact strength while moderately reducing Young's modulus, but still at the expense of rheological properties.

[0013] Therefore, in polyolefin compositions containing recycled polyolefins, a good balance of viscosity, rigidity, and impact strength remains strongly desired.

[0014] In particular, there is a strong demand for an upgraded polyolefin composition containing recycled polyolefin, which has an increased MFR while maintaining desirable mechanical properties as compared to the recycled polyolefin alone.

[0015] The present invention is based on the surprising discovery that combining a random alpha-olefin copolymer with a hydrocarbon tackifier resin ("tackifier") results in a significant increase in MFR (ISO1133) while balancing mechanical properties such as yield strength (ISO527-2) and impact strength (ISO179-1). The present invention also accomplishes this using a relatively inexpensive modifier, bringing a sustainable and economical solution to the recycled polyolefin market

[0016] In one embodiment, the present invention is based on the surprising discovery that combining a random alpha-olefin copolymer with a hydrocarbon tackifier resin ("tackifier") in a polyethylene-rich recycled polyolefin composition results in a significant increase in both MFR (ISO1133) and elongation at break or elongation at yield, while balancing other mechanical properties.

[0017] In another embodiment, the present invention is based on the surprising discovery that non-rubber additional polymers such as linear low density polyethylene (LLDPE), ethylene-acrylate copolymers, and medium density polyethylene (MDPE) can be combined with at least one random alpha-olefin copolymer and at least one hydrocarbon tackifier resin to improve the impact strength of polyolefin compositions comprising recycled polyolefins.

[0018] The present invention is also based on the surprising discovery that a new process comprising visbreaking a recycled polyolefin, followed by melt blending with at least one random alpha-olefin copolymer, provides a significant increase in MFR while balancing mechanical properties such as yield strength and impact strength. More specifically, a process has been discovered comprising: 1) extruding at least one recycled polyolefin in the presence of at least one radical initiator to produce a visbroken recycled polyolefin; and 2) contacting (A) from about 60 to about 96 wt% of said visbroken recycled polyolefin, (B) from about 2 to about 20 wt% of at least one random alpha-olefin copolymer, and (C) optionally, from about 2 to about 20 wt% of at least one tackifier, wherein the polyolefin composition has a weight ratio of random alpha-olefin copolymer to said optional tackifier of from about 0.2 to about 5.0, and the extruded visbroken polyolefin composition has a melt flow rate increase of from about 5 to about 400% as compared to the same polyolefin composition that has not been melt blended with the random alpha-olefin copolymer and optional tackifier, and the polyolefin composition has a melt flow rate increase of from about 5 to about 1500% as compared to the same polyolefin composition that has not undergone said visbreaking extrusion and melt blending with the random alpha-olefin copolymer and optional tackifier. SUMMARY OF THE INVENTION

[0019] One embodiment of the present invention provides a polyolefin composition comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, and C) about 2 to about 20% by weight of at least one tackifier, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, and the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier.

[0020] In another embodiment, a process is provided for producing a polyolefin composition, comprising: 1) extruding at least one recycled polyolefin in the presence of at least one radical initiator (E) to produce an extruded bis-breaking recycled polyolefin; and 2) melt-blending (A) about 60 to about 96% by weight of the extruded recycled polyolefin, (B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, and (C) optionally about 2 to about 20% by weight of at least one tackifier, and (D) optionally at least one additional polymer, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, and the extruded bis-breaking polyolefin composition has an increase in melt flow rate of about 5 to about 1500% compared to the recycled polyolefin.

[0021] In another embodiment, a process is provided for producing a polyolefin composition, comprising melt-blending (A) at least one recycled polyolefin in about 60 to about 96% by weight, B) at least one random alpha-olefin copolymer in about 2 to about 20% by weight, C) at least one tackifier in about 2 to about 20% by weight, and D) at least one additional polymer optionally, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, and the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer, tackifier, and optional additional polymer.

[0022] In another embodiment, a polyolefin composition is provided comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, C) at least one tackifier, and D) about 1 to about 60% by weight of at least one additional polymer, wherein the polyolefin composition has a weight ratio of about 0.2 to about 5.0 random alpha-olefin copolymer to tackifier, and the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer, tackifier, and additional polymer. [Brief explanation of the drawing]

[0023] The present invention will now be described with reference to the drawings. The accompanying drawings incorporated herein and constituting part of this specification illustrate certain embodiments and, together with the description herein, serve to illustrate certain principles of the structures and methods disclosed herein. [Figure 1] The linearity variable in the percentage of amorphous poly(alpha)olefins is shown. [Figure 2]This shows the linearity variable in the percentage of hydrogenated amorphous poly(alpha)olefins. [Modes for carrying out the invention]

[0024] The following detailed description is provided to give the reader a more complete understanding of certain specific embodiments, features, and details of the invention and should not be construed as limiting the scope of the invention.

[0025] Certain terms used throughout this disclosure are defined below to facilitate understanding of the invention. Additional definitions are provided throughout this disclosure.

[0026] Any term not explicitly defined in this application should be understood to have a meaning generally accepted by those skilled in the art. Where the construction of a term renders it meaningless or essentially meaningless in its context, the definition of the term should be taken from a standard dictionary.

[0027] The use of numerical values ​​within the various ranges specified herein is considered an approximation, unless expressly indicated otherwise, as if the word “about” preceded both the minimum and maximum values ​​within the stated ranges. In this context, the term “about” means encompassing deviations of 1%, 2%, 3%, 4%, or 5% or less from the stated value ± the stated value. In this way, using small fluctuations above and below the stated ranges can achieve substantially the same results as values ​​within the ranges. In addition, these range disclosures are intended as continuous ranges encompassing all values ​​between the minimum and maximum values.

[0028] Unless otherwise specified, % solids or wt% refers to the total weight of a particular formulation, composition, compound, or masterbatch.

[0029] As used herein, “polymer” may refer to homopolymers, copolymers, interpolymers, terpolymers, etc. A “polymer” has two or more identical or different monomer-derived units. A “homopolymer” is a polymer having identical derived monomer units. A “copolymer” is a polymer having two or more derived monomer units that are different from each other. A “terpolymer” is a polymer having three monomer-derived units that are different from each other. The term “different” used to refer to monomer-derived units means that the monomer-derived units differ from each other by at least one atom or are isomerically different. Thus, the definition of copolymer, as used herein, includes terpolymers, etc. Similarly, the definition of polymer, as used herein, includes copolymers, etc.

[0030] The present invention provides a polyolefin composition comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, and C) about 2 to about 20% by weight of at least one tackifier, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, and the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier.

[0031] For the purposes of this specification and subsequent claims, the term “recycled polyolefin” is used to refer to materials recovered from post-consumer waste (PCR), industrial waste, and / or post-industrial waste (PIR), as opposed to unused polymers.

[0032] "Post-consumer waste" refers to objects that have completed at least one use cycle (or life cycle), i.e., have already fulfilled their primary purpose, while "post-industrial waste" and "industrial waste" refer to manufacturing scrap that does not typically reach consumers. The term "unused" means newly generated materials and / or objects that have not yet been recycled and are prior to their first use.

[0033] Recycled polyolefins include at least one polymer selected from the group consisting of ethylene polymers and propylene polymers. Any type of ethylene polymer or propylene polymer known in the art can be used as a recycled polyolefin known in the art.

[0034] Ethylene polymers, also known as "polyethylene," include polyethylene homopolymers and ethylene-alpha-olefin copolymers containing at least 50 mol% ethylene-derived units. Ethylene-alpha-olefin copolymers may have an alpha-olefin comonomer content of more than 5% by weight, more than 7% by weight, or more than 10% by weight, based on the total weight of polymerizable monomers.

[0035] Ethylene-alpha-olefin copolymer is composed of one or more C3-C3 copolymers. 40 It contains a comonomer that includes olefin derivative units. In another embodiment, the ethylene-alpha-olefin copolymer is C3-C 40 Contains olefin-derived units. C3~C 40 Olefin monomers may be linear, branched, or cyclic. C3~C 40 The cyclic olefin may be strained or unstrained, monocyclic or polycyclic, and may optionally contain a heteroatom and / or one or more functional groups.

[0036] Abstract C3-C 40Examples of olefin comonomers include, but are not limited to, propylene, butene, pentene, hexene, heptene, octene, nonene, decene, undecene, dodecene, norbornene, norbomadien, dicyclopentadiene, cyclopentene, cycloheptene, cyclooctene, cyclooctadiene, cyclododecene, 7-oxanorbomene, 7-oxanorbornadiene, and their substituted derivatives and isomers. Examples of substituted derivatives and isomers include, but are not limited to, 1,5-cyclooctadiene, 1-hydroxy-4-cyclooctene, 1-acetoxy-4-cyclooctene, 5-methylcyclopentene, and norbomadiene.

[0037] Exemplary comonomers include, but are not limited to, propylene, isobutylene, 1-butene, 1-pentene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, and 1-octene, unconjugated dienes, polyenes, butadiene, isoprene, pentadiene, hexadiene (e.g., 1,4-hexadiene), octadiene, styrene, halosubstituted styrene, alkylsubstituted styrene, tetrafluoroethylene, vinylbenzocyclobutene, naphthenic compounds, cycloalkenes (e.g., cyclopentene, cyclohexene, cyclooctene), and mixtures thereof. Typically, ethylene is a C3-C3 compound. 20 It is copolymerized with alpha-olefins.

[0038] Exemplary diene or triene comonomers include, but are not limited to, 7-methyl-1,6-octadiene; 3,7-dimethyl-1,6-octadiene; 5,7-dimethyl-1,6-octadiene; 3,7,11-trimethyl-1,6,10-octatriene; 6-methyl-1,5-heptadiene; 1,3-butadiene; 1,3-pentadiene, norbornadiene, 1,6-heptadiene; 1,7-octadiene; 1,8-nonadiene; 1,9-decadiene; 1,10-undecadiene; norbornene; tetracyclododecene; or mixtures thereof. In another embodiment, the diene or triene comonomer is at least one selected from the group consisting of butadiene, hexadiene, and octadiene. In yet another embodiment, the diene or triene comonomer is 1,4-hexadiene; 1,9-decadiene; 4-methyl-1,4-hexadiene; 5-methyl-1,4-hexadiene; dicyclopentadiene; as well as 5-ethylidene-2-norbornene (ENB), 1,3-butadiene, 1,3-pentadiene, norbornadiene, and dicyclopentadiene; C8 to C including styrene, o-, m-, and p-methylstyrene, divinylbenzene, vinylbiphenyl, vinylnaphthalene 40 vinyl aromatic compounds; as well as halogen-substituted C8 to C such as chlorostyrene and fluorostyrene 40 is at least one selected from the group consisting of vinyl aromatic compounds.

[0039] Polyethylene polymers include, but are not limited to, low density polyethylene, linear low density polyethylene, medium density polyethylene, high density polyethylene, ultra-low density polyethylene, and ultra-high molecular weight polyethylene.

[0040] Low density polyethylene is generally prepared at high pressure using free radical initiators, or in a gas phase process using Ziegler-Natta or vanadium catalysts. Low density polyethylene typically has a density of from about 0.916 g / cm 3 to about 0.950 g / cm 3It has a density in the range of [value]. Typical low-density polyethylene produced using free radical initiators is known in the industry as "LDPE". LDPE is also known as "branched" or "heterogeneously branched" polyethylene because a relatively large number of long-chain branches extend from the main polymer backbone.

[0041] 0.916 g / cm³ 3 ~0.950g / cm 3 Polyethylenes of the same density range that are linear and do not contain long-chain branches are known as linear low-density polyethylene (LLDPE) and are typically produced using conventional Ziegler-Natta catalysts or metallocene catalysts. "Linear" means that the polyethylene has little to no long-chain branches.

[0042] Medium-density polyethylene (MDPE) typically has a density of 0.926–0.940 g / cm³. 3 It has a density and is generally produced by low-pressure polymerization techniques using transition metal catalysts such as Ziegler-Natta catalysts or metallocene catalysts.

[0043] High-density polyethylene (HDPE) typically has a density of approximately 0.950 g / cm³. 3 It has a higher density and is generally prepared using a Ziegler-Natta catalyst or a chromium catalyst.

[0044] Ultra-high molecular weight polyethylene (UHMWPE) refers to HDPE with a much higher molecular weight, typically 10 times higher. UHMWPE is typically produced using metallocene catalysts.

[0045] Ultra-low density polyethylene (ULDPE) has a density of approximately 0.916 g / cm³. 3It can be produced by several different processes that produce polyethylene with a density of less than 0.890 g / cm³. In other embodiments, ULDPE has a density of about 0.890 g / cm³. 3 ~Approx. 0.915g / cm 3 Or approximately 0.900 g / cm³ 3 ~Approx. 0.915g / cm 3 It has a density within that range.

[0046] Propylene polymers, also known as "polypropylene," include propylene homopolymers and propylene copolymers containing at least 50 mol% of propylene derivative units. The term "polypropylene" includes, but is not limited to, atactic polypropylene (aPP), isotactic polypropylene (iPP), defined as having at least 10% or more isotactic pentads, high isotactic polypropylene, defined as having 50% or more isotactic pentads, syndiotactic polypropylene (sPP), defined as having 10% or more syndiotactic pentads, homopolymer polypropylene (hPP), also called propylene homopolymer or homopolypropylene, and so-called random copolymer polypropylene (RCP), also called propylene random copolymer. In this specification, RCP may include copolymers of propylene and 1 to 10% by weight of olefin derivative units selected from ethylene and C4-C8 alpha-olefins. When polyolefins contain less than 10% isotactic pentads and syndiotactic pentads, they are considered "atactic" and are also called "amorphous."

[0047] Propylene copolymer, also known as "propylene-alpha-olefin copolymer," is a copolymer in which propylene is replaced by ethylene or one C4-C4 molecule. 20It contains a polymer copolymerized with alpha-olefin.

[0048] Suitable comonomers for copolymerization with propylene include, but are not limited to, ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-unidecene, 1-dodecene, 4-methyl-1-pentene, 4-methyl-1-hexene, 5-methyl-1-hexene, vinylcyclohexene, and styrene.

[0049] Exemplary propylene copolymers include propylene / ethylene, propylene / 1-butene, propylene / 1-hexene, propylene / 4-methyl-1-pentene, propylene / 1-octene, propylene / ethylene / 1-butene, propylene / ethylene / ethylidene norbornene (ENB), propylene / ethylene / 1-hexene, propylene / ethylene / 1-octene, propylene / styrene, and derivative units of propylene / ethylene / styrene.

[0050] Propylene copolymers contain ethylene derivative units or C4-C4 in the ranges of 5%-50% by weight, 6%-40% by weight, 7%-35% by weight, 8%-20% by weight, and 10%-15% by weight of the copolymer. 20 The copolymer contains alpha-olefin derivative units (or "comonomer derivative units"). The propylene-alpha-olefin copolymer may also contain derivative units of two different comonomer derivative units. Furthermore, these copolymers and terpolymers may contain diene-derived units. The amount of diene-derived units may be in the range of 10% by weight or less of diene-derived units (or "diene"), 8% by weight or less, 5% by weight or less, or 3% by weight or less, based on the total weight of the terpolymer. In another embodiment, the amount of diene-derived units may be in the range of 0.1% to 10% by weight, 0.5% to 8% by weight, and 1% to 5% by weight.

[0051] Suitable dienes include, but are not limited to, 1,4-hexadiene, 1,6-octadiene, 5-methyl-1,4-hexadiene, 3,7-dimethyl-1,6-octadiene, dicyclopentadiene (DCPD), ethylidene norbornene (ENB), norbornadiene, 5-vinyl-2-norbornene (VNB), or combinations thereof.

[0052] Propylene copolymers can be random or block copolymers, propylene-based terpolymers, branched polypropylenes, or any variation thereof (each possessing several properties). Random propylene copolymers have comonomer-derived units randomly distributed along the polymer backbone. Block copolymers have comonomer-derived units that occur in long sequences.

[0053] The propylene homopolymers and copolymers described herein can be produced using any suitable catalyst and / or process known for producing polypropylene homopolymers and copolymers. The polypropylene homopolymers and copolymers may have conventional compositions and may be produced by gas-phase, slurry, or solution-type processes.

[0054] The presence of impurities in recycled polyolefins is implied by the definition of waste and is known to those skilled in the art. Impurities include both substances intentionally and unintentionally added to the wastewater stream. These impurities include, but are not limited to, other polymers, additives, and fillers.

[0055] Such polymers that may be present as impurities in recycled polyolefins include, but are not limited to, ethylene vinyl acetate, ethylene methyl acrylate, copolymers of acrylic acid, polymethyl methacrylate, or any other polymers polymerizable by high-pressure free radical processes, polyvinyl chloride, polybutene-1, isotactic polybutene, acrylonitrile butadiene styrene (ABS) resin, ethylene propylene rubber (EPR), vulcanized EPR, ethylene propylene diene monomer rubber (EPDM), block copolymers, styrene-based block copolymers, polyamides, polycarbonates, polyethylene terephthalate (PET) resin, crosslinked polyethylene, copolymers of ethylene and vinyl alcohol (EVOH), polymers containing aromatic monomers, polyesters, polyacetals, polyvinylidene fluoride, polyethylene glycol, polyisobutylene, and / or combinations thereof. An example of a polymer containing aromatic monomers is polystyrene.

[0056] Such additives that may be present as impurities in recycled polyolefins include, but are not limited to, antioxidants (AOs), antacids, anti-tack additives, plasticizers, tackifiers, UV stabilizers, anti-blocking agents, crosslinking agents, mold release agents, antistatic agents, antimicrobial agents, biocides, foaming agents, leavening agents, clarifying agents, flame retardants, catalysts, pigments, colorants, dyes, waxes, or combinations thereof. Examples of antioxidants include, but are not limited to, sterically hindered phenols such as IRGANOX® 1010 or IRGANOX® 1076 by BASF, phosphorus-based AOs such as IRGAFOS® 168 by BASF, sulfur-based AOs such as Irganox PS-802 FL® by BASF, nitrogen-based AOs such as 4,4'-bis(1,1'-dimethylbenzyl)diphenylamine, and AO blends. Examples of antacids include, but are not limited to, calcium stearate, sodium stearate, zinc stearate, magnesium oxide and zinc oxide, synthetic hydrotalcite, lactate and lactylate, and combinations thereof. Examples of tackifiers include, but are not limited to, polybutene, terpene resins, aliphatic and aromatic hydrocarbon resins, alkali metals and glycerol stearate, and hydrogenated rosin. Examples of UV stabilizers include, but are not limited to, bis-(2'2'6'6-tetramethyl-4-piperidyl)-sebacate. Examples of nucleating agents include, but are not limited to, sodium benzoate and 1,3:2,4-bis(3,4-dimethylobenzylideno)sorbitol. Examples of antiblocking agents include, but are not limited to, diatomaceous earth, synthetic silica, silicates, and synthetic zeolites. Examples of silicates include, but are not limited to, kaolin, sodium aluminum silicate, calcined kaolin, aluminum silicate, or calcium silicate. Examples of antistatic agents include, but are not limited to, glycerol esters, ethoxyamines, and ethoxyamides. Typically, these additives can be present in amounts of about 100 to 2000 ppm for each individual additive.

[0057] Examples of fillers that may be present as impurities in recycled polyolefins include, but are not limited to, coal, fly ash, calcium carbonate, barium sulfate, carbon black, metal oxides, inorganic materials, natural materials, alumina trihydrate, magnesium hydroxide, bauxite, talc, mica, barite, kaolin, silica, post-consumer glass, or post-industrial glass, synthetic and natural fibers, or any combination thereof. The fillers may be organic, inorganic, or a combination of both (e.g., in different forms).

[0058] In one embodiment, the percentage of impurities in the recycled polyolefin is at least 0.1, 0.5, 1, 5, 10, 15, 20, 25, 30, or 35% by weight and / or 90, 85, 80, 75, 70, 65, or 60% by weight or less, based on the weight of the recycled polyolefin. In other embodiments, the percentage of impurities may be in the range of about 0.1 to about 86% by weight, about 0.5 to about 85% by weight, about 1 to about 80% by weight, about 5 to about 75% by weight, about 10 to about 70% by weight, about 15 to about 65% by weight, and about 20 to about 60% by weight, based on the weight of the recycled polyolefin in the polyolefin composition. Other amounts below and above these ranges may exist.

[0059] In some other embodiments of several types of recycled polyolefins, the percentage of impurities in the recycled polyolefin is about 0.1 to about 10% by weight, about 0.1 to about 5% by weight, about 0.5 to about 5% by weight, and about 0.5 to about 3% by weight, based on the weight of the recycled polyolefin in the polyolefin composition. Other amounts below and above these ranges may exist.

[0060] In at least one other embodiment, the percentage of filler in recycled polyolefin is about 5 to about 85% by weight, about 10 to about 85% by weight, about 20 to about 85% by weight, about 30 to about 85% by weight, about 40 to about 85% by weight, and 50 to about 85% by weight, based on the weight of recycled polyolefin in the polyolefin composition. Other amounts below and above these ranges may exist.

[0061] For the purposes of the present invention, the weight percentage of recycled polyolefin shall be deemed to be the weight percentage of recycled polyethylene-rich polyolefin and / or polypropylene-rich recycled polyolefin, including impurities.

[0062] In other embodiments of the present invention, the amount of recycled polyolefin in the polyolefin composition may be in the range of at least 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, or 89% by weight and / or 90, 91, 92, 93, 94, 95, or 96% by weight or less, based on the weight of the polyolefin composition. Other ranges may be about 60 to about 96% by weight, about 65 to about 90% by weight, about 70% to about 85% by weight, and about 75% to about 85% by weight, based on the weight of the polyolefin composition.

[0063] A recycled polyolefin is considered a polyethylene-rich recycled polyolefin if it contains at least 50% by weight, at least 55% by weight, at least 60% by weight, at least 65% by weight, at least 70% by weight, at least 80% by weight, at least 85% by weight, at least 90% by weight, at least 95% by weight, at least 97% by weight, or at least 98% by weight of ethylene polymer. In such a polyethylene-rich recycled polyolefin, polyethylene is also called the main component.

[0064] A recycled polyolefin is considered a polypropylene-rich recycled polyolefin if it contains at least 50% by weight, at least 55% by weight, at least 60% by weight, at least 65% by weight, at least 70% by weight, at least 75% by weight, at least 80% by weight, at least 85% by weight, at least 90% by weight, at least 95% by weight, at least 97% by weight, or at least 98% by weight of propylene polymer. In such a polypropylene-rich recycled polyolefin, polypropylene is also called the main component.

[0065] Random alpha-olefin polymers may be any known in the art, including but not limited to homopolymers and copolymers. Random alpha-olefin copolymers may be any known in the art. In one embodiment of the present invention, random alpha-olefin copolymers, also called amorphous polyolefins (APO) or amorphous poly-alpha-olefins (APAO), include but are not limited to amorphous propylene-ethylene copolymers that can contain various amounts of ethylene or propylene. For example, a propylene-ethylene copolymer may contain at least 1, 3, 5, 7, 10, 12, 14, 15, 17, 18, or 20 and / or 70, 65, 60, 55, 50, 45, 40, 35, 30, 27, or 25% by weight of ethylene. Furthermore, propylene-ethylene copolymers may contain ethylene in the range of about 1 to about 70, about 3 to about 65, about 5 to about 60, about 7 to about 55, about 10 to about 50, about 12 to about 45, about 14 to about 40, about 15 to about 35, about 17 to about 30, about 18 to about 27, or about 20 to about 25 weight percent. For example, a propylene-ethylene copolymer may contain at least 40, 50, 60, 65, or 70 weight percent and / or 99, 95, 90, 85, or 80 weight percent or less of propylene. Furthermore, a propylene-ethylene copolymer may contain propylene in the range of about 40 to about 99, about 50 to about 95, about 60 to about 90, about 65 to about 85, or about 70 to about 80 weight percent.

[0066] Furthermore, APO has one or more C4~C 10 It may contain propylene-ethylene copolymers that can contain derived units of alpha-olefins. These C4-C 10Examples of alpha-olefins include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and combinations thereof. According to one or more embodiments, the copolymer contains at least 0.5, 1, 2, 3, 4, or 5 weight percent and / or 40, 30, 25, 20, 15, or 10 weight percent of at least one C4-C4 copolymer. 10 It may contain alpha-olefins. Furthermore, the copolymer may contain at least one C4-C in the range of about 0.5-40, about 1-30, about 2-25, about 3-20, about 4-15, or about 5-10 weight percent. 10 It may contain alpha-olefins. Examples of commercially available random alpha-olefin copolymers include Aerafin® 17 and Eastoflex® E1200 from Eastman Chemical Company.

[0067] Furthermore, APO may include polypropylene homopolymers. Exemplary commercially available random alpha-olefin homopolymers include Eastoflex® P1010 and Eastoflex® P1023 from Eastman Chemical Company.

[0068] In one embodiment, the random alpha-olefin copolymer may have a number-average molecular weight of 25,000 mol / g or less and 10,000 mol / g or less. In other embodiments, the number-average molecular weight may be 2,500 to 25,000 g / mol and / or 4,500 to 10,000 g / mol. The polydispersity index of the random alpha-olefin copolymer may be in the range of about 4.0 to about 10.0 or about 5.0 to about 7.5.

[0069] Number-average molecular weight is measured using a Malvern Viscotek HT-350A High Temperature Gel Permeation Chromatograph (HTGPC) equipped with two Viscotek VE1122 pumps, a Viscotek Model 430 vortex heater stirrer autosampler, a VE7510 GPC degasser, an HTGPC Module 350A oven, a Microlab 500 series autosyringe for sample preparation, and a triple detection system consisting of a combination of laser light scattering, refractometer, and differential viscosity detector. The GPC contains a 1×PLGel 5 micron Guard 50×7.5 mm column and a 2×PLGel 5 micron mixed-C 300×7.5 mm column with 1,2,4-trichlorobenzene flowing as solvent at a flow rate of 0.7 ml / min at 135°C. Each sample is weighed to 50-70 mg and mixed with 10 mL of 1,2,4-trichlorobenzene to prepare a blend of 5.0-7.0 mg / mL. The vials are placed in a Viscotek Model 430 vortex heater stirrer autosampler and equilibrated at room temperature for approximately 1 hour with stirring using a magnetic stirrer bar. The samples are then heated at 135°C for up to 4 hours. Two injections are used for each sample, and a chromatogram is collected for each injection. The samples are analyzed by conventional GPC using a single narrow polystyrene standard calibration, light scattering, triple detection, and universal calibration. The same Malvern OmniSEC software is used for light scattering data analysis, conventional GPC analysis, triple detection analysis, and universal calibration analysis.

[0070] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) are determined for each sample using Malvern OmniSEC software. The polydispersity index (PDI) is calculated by dividing the weight-average molecular weight by the number-average molecular weight (PDI = Mw / Mn).

[0071] Random alpha-olefin copolymers may have a glass transition temperature (Tg) (differential scanning calorimetry according to ASTM D3418-15, 20°C / min) of -10°C or lower, -25°C or lower, or -35°C or lower.

[0072] Tackifiers, also known as "tackifier resins," include, but are not limited to, alicyclic hydrocarbon resins, C5 hydrocarbon resins, C5 / C9 hydrocarbon resins, aromatically modified C5 resins, C9 hydrocarbon resins, pure monomer resins, C5 resins and C9 resins, terpene resins, terpene phenol resins, terpene styrene resins, rosin esters, modified rosin esters, fully or partially hydrogenated rosin liquid resins, fully or partially hydrogenated rosin esters, fully or partially hydrogenated modified rosin resins, fully or partially hydrogenated rosin alcohols, fully or partially hydrogenated C5 resins, fully or partially hydrogenated C5 / C9 resins, fully or partially hydrogenated aromatically modified C5 resins, fully or partially hydrogenated C9 resins, fully or partially hydrogenated pure monomer resins, fully or partially hydrogenated C5 / alicyclic resins, fully or partially hydrogenated C5 / alicyclic / styrene / C9 resins, fully or partially hydrogenated alicyclic resins, and combinations thereof. Examples of commercially available tackifiers include Regalite® and Eastotac® H hydrocarbon resins from Eastman Chemical Company. Furthermore, tackifiers may contain functional groups.

[0073] As used herein, the term "PMR" means pure monomer resin. Pure monomer resins are produced from the polymerization of styrenic monomers such as styrene, alpha-methylstyrene, vinyltoluene, and other alkyl-substituted styrenes. Pure monomer resins are produced by any method known in the art. The pure monomer feedstock for the production of pure monomer resins is, in some cases, a synthetically produced or highly purified monomer species. For example, styrene can be produced from ethylbenzene, or alpha-methylstyrene from cumene. In one embodiment, the pure monomer hydrocarbon resin is prepared by cationic polymerization of styrenic monomers such as styrene, alpha-methylstyrene, vinyltoluene, and other alkyl-substituted styrenes using a Friedel-Crafts polymerization catalyst such as a Lewis acid (e.g., boron trifluoride (BF3), complexes of boron trifluoride, aluminum trichloride (AlCl3) and alkylaluminum chloride). Solid acid catalysts can also be utilized to produce pure monomer resins. The pure monomer resins disclosed herein are non-hydrogenated resins, partially hydrogenated resins, or fully hydrogenated resins. As used herein, the term "hydrogenated" is also alternatively indicated by the abbreviation "H2", and when H2 is used before or after the resin type, such as "PMR H2" and "C5 H2", it is intended to indicate that the resin type is hydrogenated or partially hydrogenated. When "H2" is used herein, "H2" is meant to encompass both fully hydrogenated resin samples and partially hydrogenated resin samples. Accordingly, "H2" refers to a state in which the resin is fully hydrogenated, or at least partially hydrogenated. Pure monomer resins are optionally obtained from Eastman Chemical Company (Kingsport, TN, US) as Piccolastic® styrenic hydrocarbon resins, Kristalex® styrenic / alkylstyrenic hydrocarbon resins, Piccotex® alkylstyrenic hydrocarbon resins, and Regalrez® hydrogenated or partially hydrogenated pure monomer resins.

[0074] As used herein, the term “C5 resin” means an aliphatic C5 hydrocarbon resin produced from the polymerization of monomers containing C5 and / or C6 olefin species that boil at a range of about 20°C to about 200°C at atmospheric pressure. These monomers are typically produced from petroleum processing, e.g., cracking. The aliphatic C5 hydrocarbon resins of the present invention can be produced by any method known in the art. In one embodiment, the aliphatic C5 hydrocarbon thermoplastic resin is prepared by cationic polymerization of cracked petroleum feedstock containing C5 and C6 paraffins, olefins, and diolefins, also called “C5 monomers.” These monomer streams consist of cationic polymerizable monomers such as 1,3-pentadiene, which are major reactive components along with cyclopentene, pentene, 2-methyl-2-butene, 2-methyl-2-pentene, cyclopentadiene, and dicyclopentadiene. Polymerization is catalyzed using Friedel-Crafts polymerization catalysts such as Lewis acids (e.g., boron trifluoride (BF3), a complex of boron trifluoride, aluminum trichloride (AlCl3), and alkylaluminum chloride). In addition to the reactive components, non-polymerizable components in the feed include saturated hydrocarbons that may be co-distilled with unsaturated components such as pentane, cyclopentane, or 2-methylpentane. Aliphatic C5 hydrocarbon resins can also be produced using solid acid catalysts. Aliphatic C5 hydrocarbon resins include non-hydrogenated resins, partially hydrogenated resins, or fully hydrogenated resins. Aliphatic C5 resins can be obtained from Eastman Chemical Company (Kingsport, TN, US) as Piccotac® C5 and Eastotac® C5 H2 resins.

[0075] As used herein, the term “C5 / C9 resin” refers to an aliphatic / aromatic hydrocarbon C5 / C9 resin produced by the polymerization of monomers comprising at least one unsaturated aromatic C8, C9, and / or C10 species that boil in the range of about 100°C to about 300°C at atmospheric pressure, and at least one monomer comprising C5 and / or C6 olefin species that boil in the range of about 20°C to about 200°C at atmospheric pressure. In one embodiment, the C5 and / or C6 species include paraffins, olefins, and diolefins, also called “C5 monomers.” These monomer streams consist of cationic polymerizable monomers such as 1,3-pentadiene, which are major reactive components along with cyclopentene, pentene, 2-methyl-2-butene, 2-methyl-2-pentene, cyclopentadiene, and dicyclopentadiene. In one embodiment, the unsaturated aromatic C8, C9, and / or C10 monomers are derived from petroleum distillates resulting from naphtha cracking and are called “C9 monomers.” These monomer streams consist of cationic polymerizable monomers such as styrene, alpha-methylstyrene, beta-methylstyrene, vinyltoluene, indene, dicyclopentadiene, divinylbenzene, and other alkyl-substituted derivatives of these components. Cationic polymerization is sometimes catalyzed using Friedel-Crafts polymerization catalysts such as Lewis acids (e.g., boron trifluoride (BF3), a complex of boron trifluoride, aluminum trichloride (AlCl3), and alkylaluminum chloride). Solid acid catalysts are also used to produce aliphatic / aromatic C5 / C9 hydrocarbon thermoplastic resins. In addition to reactive components, non-polymerizable components include aromatic hydrocarbons such as xylene, ethylbenzene, cumene, ethyltoluene, indan, methylindan, naphthalene, and other similar species. In some embodiments, the non-polymerizable components of the supply stream are incorporated into the resin via alkylation reactions. Aliphatic / aromatic C5 / C9 hydrocarbon resins include non-hydrogenated resins, partially hydrogenated resins, or hydrogenated resins. Aliphatic / aromatic C5 / C9 thermoplastic resins can be obtained from Eastman Chemical Company as Piccotac® resins. The proportion of C5-C9 is not limited.In other words, the amount of C5 monomer in a C5 / C9 resin can be anywhere from 0.1% to 100%, and vice versa; the amount of C9 monomer in a C5 / C9 resin can be anywhere from 0.1% to 100%.

[0076] As used herein, the term “C9 resin” refers to an aromatic C9 hydrocarbon resin, which is a resin produced from the polymerization of monomers containing unsaturated aromatic C8, C9, and / or C10 species that boil in the range of about 100°C to about 300°C at atmospheric pressure. These monomers are typically produced from petroleum processing, e.g., cracking. The aromatic C9 hydrocarbon thermoplastic resins of the present invention can be produced by any method known in the art. In one embodiment, the aromatic C9 hydrocarbon resin is prepared by the cationic polymerization of aromatic C8, C9, and / or C10 unsaturated monomers derived from petroleum distillates resulting from naphtha cracking, and is referred to as “C9 monomers.” These monomer streams consist of cationic polymerizable monomers such as styrene, alpha methyl styrene (AMS), beta-methyl styrene, vinyltoluene, indene, dicyclopentadiene, divinylbenzene, and other alkyl-substituted derivatives of these components. In some embodiments of the C9 resin, aliphatic olefin monomers having 4 to 6 carbon atoms are also present in the polymerization. Polymerization is sometimes catalyzed using Friedel-Crafts polymerization catalysts such as Lewis acids (e.g., boron trifluoride (BF3), a complex of boron trifluoride, aluminum trichloride (AlCl3), and alkylaluminum chloride). In addition to the reactive components, non-polymerizable components include, but are not limited to, aromatic hydrocarbons such as xylene, ethylbenzene, cumene, ethyltoluene, indan, methylindan, naphthalene, and other similar chemical species. In some embodiments, the non-polymerizable components of the supply stream are incorporated into the thermoplastic resin via alkylation reactions. C9 hydrocarbon resins include non-hydrogenated resins, partially hydrogenated resins, or fully hydrogenated resins. Aromatic C9 hydrocarbon resins can be obtained as Picco® C9 resins, and aliphatic hydrogenated and aliphatic / aromatic partially hydrogenated C9 H2 hydrocarbon resins can be obtained from Eastman Chemical Company as Regalite® resins.

[0077] As used herein, the term “DCPD resin” means dicyclopentadiene (DCPD), most commonly formed by ring-opening metathesis polymerization (ROMP) or thermal polymerization of dicyclopentadiene in the presence of a strong acid catalyst such as maleic acid or an aqueous sulfuric acid solution. Dicyclopentadiene is also, in some embodiments, formed from two cyclopentadiene molecules by a Diels-Alder reaction and exists in two stereoisomers: endo-DCPD and exo-DCPD. Typically, more than 90% of the DCPD molecules present in commercially grade DCPD are of the endo form. Examples of DCPD thermoplastic resins include aromatically modified DCPD resins, as well as hydrogenated, partially hydrogenated, and unhydrogenated resins; however, in most examples herein, only H2 DCPD is described, as H2 DCPD is the most readily available commercially. Aromatically modified DCPD is also intended as a DCPD resin. Aromatic modification is, for example, by C9 resin oil, styrene, or alpha-methylstyrene (AMS). Hydrogenated and partially hydrogenated DCPD, as well as hydrogenated and partially hydrogenated aromatically modified DCPD resins, are commercially available as Escorez® 5000 series resins (ExxonMobil Chemical Company, TX, US).

[0078] As used herein, the terms “terpene resin” or “polyterpene resin” refer to a resin produced from at least one terpene monomer. For example, polyterpene thermoplastic resins can be obtained by polymerizing α-pinene, β-pinene, d-limonene, and dipentene in the presence of aluminum chloride. Other examples of polyterpene thermoplastic resins include Sylvares® TR 1100 and Sylvatraxx® 4125 terpene thermoplastic resins (AZ Chem Holdings, LP, Jacksonville, FL, US), and Piccolyte® A125 terpene thermoplastic resin (Pinova, Inc., Brunswick, GA, US). Terpene resins can also be modified with aromatic compounds. Sylvares® ZT 105LT and Sylvares® ZT 115 LT terpene resins are aromatically modified (AZ Chem Holdings, LP, Jacksonville, FL, US).

[0079] The above definition of certain types of thermoplastic resins, including DCPD, PMR, C5, C9, C5 / C9, terpenes, and their hydrogenated, partially hydrogenated, and non-hydrogenated versions, should be understood to encompass similar types of resins produced by mixing or blending different feedstocks to produce a heterogeneous mixture of feedstocks used to produce the thermoplastic resin. Furthermore, with respect to PMR and terpene resins discussed herein, it should be understood that these resins encompass a variety of known derivatives of such resins, such as phenol-modified and rosin-modified versions of the resins.

[0080] The tackifier has a glass transition temperature (Tg) (differential scanning calorimetry according to ASTM D3418-15, 20°C / min) of 25°C or higher, 30°C or higher, 35°C or higher, 40°C or higher, 45°C or higher, 50°C or higher, 55°C or higher, 60°C or higher, 65°C or higher, or 70°C or higher, or 75°C or higher, or 80°C or higher, or 85°C or higher. In other embodiments, the tackifier has a glass transition temperature (differential scanning calorimetry according to ASTM D3418-15, 20°C / min) in the ranges of approximately 30°C to 90°C, approximately 35°C to 90°C, approximately 40°C to 90°C, approximately 45°C to 90°C, approximately 50°C to 90°C, approximately 55°C to 90°C, approximately 60°C to 90°C, approximately 65°C to 90°C, approximately 70°C to 90°C, approximately 75°C to 90°C, and approximately 80°C to 90°C.

[0081] The present invention relates to polyolefin compositions having improved flow properties while retaining acceptable mechanical properties. Polyethylene-rich recycled polyolefin compositions, in particular, can have improved flowability and improved elongation at break while retaining acceptable mechanical properties and / or providing a favorable balance of properties for a particular application. The present invention provides compositions comprising at least one recycled polyolefin (A), at least one random alpha-olefin copolymer (B), and at least one tackifier (C). In some embodiments, the compositions and methods described herein relate to recycled polyolefins selected from the group consisting of ethylene-rich or propylene-rich recycled polyolefins, wherein the random alpha-olefin copolymer is at least one amorphous propylene-ethylene random copolymer such as Aerafin (trademark) and Eastoflex (trademark) (Eastman Chemical), together with at least one hydrogenated C9 tackifier such as Regalite (trademark) R1125 and Plastolyn (trademark) R1140 (Eastman Chemical), and processes for producing such polyolefin compositions. In at least one embodiment, by adding low levels of a propylene-ethylene random copolymer such as Aerafin® and a hydrogenated C9 tackifier such as Regalite® to a recycled polyolefin, the flow properties, such as the melt flow rate (MFR), of the resulting polyolefin composition containing the recycled polyolefin can be improved while maintaining acceptable mechanical properties. Low molecular weight Aerafin® and Regalite® can reduce the MFR while exhibiting unexpected synergistic behavior with respect to mechanical properties. Acceptable mechanical properties are defined later in this disclosure.

[0082] The remarkably improved elongation at break results in polyethylene-rich polyolefin compositions that are less brittle, more easily demolded without breakage, and more resistant to high filler content in recycled polyolefin feedstreams and final compositions. High filler content is often used to increase the modulus of recycled polyolefin materials, with the corresponding drawback of the final composition being excessively brittle. The present invention, with its remarkably increased elongation at break, may enable the use of these highly filled recycled feedstreams in applications where the stream was previously excessively brittle. Possible applications that can benefit from the increased elongation at break and the resulting flexibility include, but are not limited to, stretch films, wrap films, agricultural films, flooring, latches and snap locks, storage containers, and garden furniture.

[0083] In at least one embodiment, recycled polyolefins may have melt flow rates (MFRs) of about 0.1 g / 10 min to about 10 g / 10 min, about 0.1 g / 10 min to about 5 g / 10 min, and about 0.1 g / 10 min to about 2 g / 10 min, as measured according to ISO 1133, 2.16 kg, at 190°C. For polyethylene-rich recycled polyolefins, the MFR may be in the range of about 10 g / 10 min or less, about 5 g / 10 min or less, about 1 g / 10 min or less, or about 0.5 g / 10 min or less, as measured according to ISO 1133, 2.16 kg, at 190°C.

[0084] In at least one embodiment, recycled polyolefins may have melt flow rates (MFRs) of about 0.1 g / 10 min to about 10 g / 10 min, about 0.1 g / 10 min to about 5 g / 10 min, and about 0.1 g / 10 min to about 2 g / 10 min, as measured in accordance with ISO 1133 at 230°C for 2.16 kg. For polypropylene-rich recycled polyolefins, the MFR may be in the range of about 10 g / 10 min or less, about 5 g / 10 min or less, about 1 g / 10 min or less, or about 0.5 g / 10 min or less, as measured in accordance with ISO 1133 at 230°C for 2.16 kg.

[0085] In at least one embodiment, the percentages of random alpha-olefin copolymer (B) and tackifier (C) in the polyolefin composition are, based on the weight of the polyolefin composition, about 4 to about 40% by weight, about 4 to about 20% by weight, about 4 to about 14% by weight, or about 7 to about 10% by weight. In another embodiment, the amounts of random alpha-olefin copolymer (B) and tackifier (C) in the polyolefin composition are, based on the weight of the polyolefin composition, at least 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15% by weight and 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, or 20% by weight or less.

[0086] The percentage of random alpha-olefin polymer may be at least 2, 3, 4, 5, 6, 7, 8, 9, or 10% by weight and / or 20, 19, 18, 17, 16, or 15% by weight or less, based on the weight of the polyolefin composition. The percentage of random alpha-olefin copolymer (B) may be in the range of about 2 to about 20% by weight, about 2 to about 10% by weight, or about 5 to about 10% by weight, based on the weight of the polyolefin composition. The percentage of tackifier (C) may be at least 2, 3, 4, 5, 6, 7, 8, 9, or 10% by weight and / or 20, 19, 18, 17, 16, 15, 14, 13, 12, or 11% by weight or less, based on the weight of the polyolefin composition. The percentages of tackifier (C) are approximately 2-20% by weight, 2-10% by weight, 2-7% by weight, and 2-5% by weight. The weight ratios of random alpha-olefin copolymer (B) to tackifier (C) are 0.2-5.0, 0.3-5.0, 0.4-5.0, 0.5-5.0, 0.6-5.0, 0.7-5.0, 0.8-5.0, 0.9-5.0, 1.0-5.0, 1.1-5.0, 1.2-5.0, 1.3-5.0, 1.4-5.0, 1.5-5.0, 1.6-5.0, 1.7-5.0, 1.8-5.0, and 1.9%. The ranges are ~5.0, 2.0~5.0, 2.1~5.0, 2.2~5.0, 2.3~5.0, 2.4~5.0, 2.5~5.0, 2.6~5.0, 2.7~5.0, 2.8~5.0, 2.9~5.0, 3.0~5.0, 3.1~5.0, 3.2~5.0, 3.3~5.0, 3.4~5.0, 3.5~5.0, 3.6~5.0, 3.7~5.0, 3.8~5.0, 3.9~5.0, or 4.0~5.0.

[0087] In one embodiment of this invention, a polyolefin composition is provided comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin having an MFR < 10 g / 10 min (ISO 1133), B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer having a Brookfield viscosity of 25,000 mPa.s or less (ASTM D 3236, 190°C), and C) about 2 to about 20% by weight of at least one tackifier having a ring-spherical softening point of 70°C or higher (ASTM E 28 or ASTM D 6090 or ASTM D 6166), wherein the weight ratio of B / C is 0.2 to 5.0, and the composition has an increase in MFR of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier. In one aspect of this embodiment, the polyolefin composition maintains acceptable mechanical properties, which are defined later in this disclosure.

[0088] In another embodiment of the present invention, a polyolefin composition comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin having an MFR < 10 g / 10 min (ISO 1133), B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer having a glass transition temperature of -10°C or lower (ASTM D 3418-15), and C) about 2 to about 20% by weight of at least one tackifier having a glass transition temperature of 25°C or higher (ASTM D 3418-15), wherein the weight ratio of B / C is 0.2 to 5.0, and the polyolefin composition has an increase in MFR of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier. In one aspect of this embodiment, the polyolefin composition maintains acceptable mechanical properties, which are defined later in this disclosure.

[0089] In another embodiment of the present invention, a polyolefin composition is provided comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin having an MFR < 10 g / 10 min (ISO 1133), B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer having a glass transition temperature of -10°C or lower (ASTM D 3418-15) and a nominal molecular weight of 25,000 g / mol or lower (ISO 16014), and C) about 2 to about 20% by weight of at least one tackifier having a glass transition temperature of 25°C or higher (ASTM D 3418-15), wherein the weight ratio of B to C is 0.2 to 5.0, and the polyolefin composition has an increase in MFR of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier. In at least one aspect of this embodiment, the polyolefin composition maintains acceptable mechanical properties, which are defined later in this disclosure.

[0090] In another embodiment of the present invention, a polyolefin composition is provided comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin having an MFR < 10 g / 10 min (ISO 1133), B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer having a glass transition temperature of -10°C or lower (ASTM D 3418-15) and a nominal molecular weight of 25,000 g / mol or lower (ISO 16014), and C) about 2 to about 20% by weight of at least one tackifier having a glass transition temperature of 45°C or higher (ASTM D 3418-15), wherein the weight ratio of B to C is 0.2 to 5.0, and the polyolefin composition has an increase in MFR of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier, and the polyolefin composition maintains acceptable mechanical properties. Acceptable mechanical properties are defined later in this disclosure.

[0091] In another embodiment of the present invention, a polyolefin composition is provided comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin having an MFR < 10 g / 10 min (ISO 1133), B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer having a glass transition temperature of -10°C or lower (ASTM D 3418-15) and a nominal molecular weight of 10,000 g / mol or lower (ISO 16014), and C) about 2 to about 20% by weight of at least one tackifier having a glass transition temperature of 45°C or higher (ASTM D 3418-15), wherein the weight ratio of B to C is 0.2 to 5.0, and the polyolefin composition has an increase in MFR of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier. In at least one aspect of this embodiment, the polyolefin composition maintains acceptable mechanical properties, which are defined later in this disclosure.

[0092] In at least one embodiment, the random alpha-olefin is a propylene homopolymer. In at least one embodiment, the at least one random alpha-olefin copolymer includes a propylene homopolymer and an ethylene-propylene copolymer.

[0093] In embodiments of the present invention, the polyolefin composition may have an increase in MFR of at least 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 200, 225, 250, 275, 300, 325, 350, 375, or 400% compared to the same polyolefin composition without random alpha-olefin copolymer and tackifier, as measured at 2.16 kg and 190°C according to ISO 1133. In other embodiments, the polyolefin composition may have an increase in MFR in the range of about 5% to about 400%, about 20% to about 400%, about 50% to about 400%, about 5% to about 200%, about 15% to about 200%, about 20% to about 200%, about 5% to about 150%, about 10% to about 150%, about 15% to about 150%, or about 30% to about 300% compared to the same polyolefin composition without random alpha-olefin copolymer and tackifier.

[0094] In addition to MFR, other rheological parameters such as spiral flow and melt viscosity can also be positively affected. Polyolefin compositions may have a spiral flow that is approximately 5% to 200%, 10% to 175%, 25% to 150%, 50% to 125%, or 50% to 100% higher than the spiral flow of the same polyolefin composition without random alpha-olefin copolymers and tackifiers. Spiral flow is measured by using a mold with a spiral 10 mm wide and 2 mm deep. The spiral length can be up to 800 mm. Polyolefin compositions may have a melt viscosity that is approximately 5% to 200%, 10% to 175%, 25% to 150%, 50% to 125%, or 50% to 100% higher than the melt viscosity of the same polyolefin composition without random alpha-olefin copolymers and tackifiers. Melt viscosity is measured with a rheometer.

[0095] Furthermore, the polyolefin composition may have at least one acceptable mechanical property selected from the group consisting of yield strength (yield strength ISO 527-2 or ASTM D 882), elongation at break, yield strength (yield strength tensile strain), Young's modulus (elastic modulus or E-modulus), tensile strength at maximum load, tensile strain at maximum load, tensile strength at break, tensile strain at break, flexural strength, toughness, film toughness, flexural modulus (flexural modulus or G-modulus ISO 178), 1% secant modulus, 2% secant modulus, unnotched Charpy impact strength, notched Charpy impact strength (notched impact strength ISO 179-1), unnotched Izod impact strength, notched Izod impact strength (ISO 180), spear impact strength (ASTM D 1709A), Elmendorf tear strength (ASTM D 1922), and fracture resistance.

[0096] As used herein, “acceptable mechanical properties” means at least one mechanical property relating to a polyolefin composition or any article containing a polyolefin composition, where the mechanical property is at least 80%, 85%, 90%, 100%, 105%, or 110% of the mechanical properties compared to the same polyolefin composition without random alpha-olefin copolymers and tackifiers. , 115%, 120%, 125%, 130%, 135%, 140%, 150%, 155%, 160%, 165%, 170%, 175%, 180%, 185%, 190%, 200%, 225%, 250%, 275%, 300%, 325%, 350%, 375%, 400%, 425%, 450%, 475%, 500%, 525%, 550%, or 575%, or approximately 600%.

[0097] In other embodiments of the present invention, at least one mechanical property of a polyolefin composition or any article containing a polyolefin composition is about 80% to about 600%, about 80% to about 550%, about 80% to about 500%, about 80% to about 450%, about 80% to about 400%, about 80% to about 350%, about 80% to about 300%, about 80% to about 250%, about 80% to about 200%, about 80% to about 150%, about 80% to about 120%, 90% to about 600%, about 90% to about 550%, Mechanical properties are "acceptable" if they fall within the following ranges: approximately 90% to 500%, approximately 90% to 450%, approximately 90% to 400%, approximately 90% to 350%, approximately 90% to 300%, approximately 90% to 250%, approximately 90% to 200%, approximately 90% to 150%, approximately 90% to 120%, approximately 100% to 600%, approximately 100% to 550%, approximately 100% to 500%, approximately 100% to 450%, approximately 100% to 400%, approximately 100% to 350%, approximately 100% to 300%, approximately 100% to 250%, approximately 100% to 200%, approximately 100% to 150%, or approximately 100% to 120%.

[0098] The various end uses of polyolefin compositions may require different balances of mechanical properties, and the values ​​of some properties may be outside this "acceptable" range, and the composition is suitable for use in that application.

[0099] In another embodiment, a polyolefin composition is provided comprising about 85 to about 96% by weight of at least one recycled polyolefin, about 2 to about 10% by weight of at least one random alpha-olefin copolymer, and about 2 to about 5% by weight of at least one tackifier, wherein the MFR of the polyolefin composition, measured according to ISO 1133 (2.16 kg at 190°C for polyethylene-rich recycled polyolefins and 230°C for polypropylene-rich recycled polyolefins), is about 25 to about 80% higher than the MFR of the same polyolefin composition without the random alpha-olefin copolymer and tackifier, the polyolefin composition has a yield strength (ISO 527-2) about 5 to about 15% lower than the yield strength (ISO 527-2) of the same polyolefin composition without the random alpha-olefin copolymer and tackifier, and a flexural modulus (ISO 178 or ASTM) about 10 to about 20% lower than the yield strength (ISO 178 or ASTM) of the same polyolefin composition without the random alpha-olefin copolymer and tackifier, It has a notched impact strength (ISO178 or ASTM D256) that is about 5 to about 15% lower than that of the same polyolefin composition without random alpha-olefin copolymers and tackifiers (D882).

[0100] In another embodiment of the present invention, a polyolefin composition or any article containing a polyolefin composition may exhibit a change in at least one property that is directly or indirectly related to a change in mechanical properties. Such properties include, but are not limited to, thermal properties (Vicat softening point, heat deflection temperature, sealing temperature, seal strength (ASTM F2029, hot tack ASTM F1921)), optical properties (haze, e.g. ASTM D1003, gloss, e.g. ASTM D2457, light transmittance, clarity), dimensional stability, heat resistance, barrier properties (MVTR, e.g. ASTM F1249, OTR, e.g. ASTM D3985), low-temperature flexibility, melting temperature, density, machine direction (MD) and transverse direction (TD) elongation ratio, enhanced uniaxial or biaxial orientation, shrinkage ratio, or melt strength.

[0101] A process for producing a polyolefin composition is provided, comprising melt-blending A) at least one recycled polyolefin in about 60 to about 96% by weight, B) at least one random alpha-olefin copolymer in about 2 to about 20% by weight, C) at least one tackifier in about 2 to about 20% by weight, and D) optionally at least one additional polymer, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, and the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier.

[0102] In another embodiment, a process is provided for producing a polyolefin composition, comprising: 1) dry blending A) at least one recycled polyolefin in about 60 to about 96% by weight, B) at least one random alpha-olefin copolymer in about 2 to about 20% by weight, C) at least one tackifier in about 2 to about 20% by weight, and D) optionally at least one additional polymer, such that the polyolefin composition has a weight ratio of about 0.2 to about 5.0 random alpha-olefin copolymer to tackifier; and 2) melt blending the components such that the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier.

[0103] Polyolefin compositions can be formed by melt-blending recycled polyolefin (A), random alpha-olefin copolymer (B), tackifier (C), and optionally additional polymer (D) by any means known in the art. In one embodiment, a dry-blended powder, flakes, pellets, or combination is used before being sent to the melt-blending step. Examples of equipment used for dry blending include, but are not limited to, a tumble blender, ribbon blender, Henschel mixer, double-cone blender, or other suitable blender, in which the recycled polyolefin (A), random alpha-olefin copolymer (B), tackifier (C), optionally at least one additive, optionally at least one filler, and optionally at least one additional polymer (D) are first brought into contact without close mixing, and then the components are melt-blended in a mixer or extruder or any other type of mixing equipment known to those skilled in the art.

[0104] In another embodiment, the polyolefin composition can be formed by directly melt-blending recycled polyolefin (A), random alpha-olefin copolymer (B), and tackifier (C), optionally at least one additive, optionally at least one filler, and optionally at least one additional polymer (D) together as powder, flakes, pellets, or a combination thereof in a mixer, a single-screw or twin-screw extruder, or other apparatus known to those skilled in the art; or the composition can be formed by directly melt-blending recycled polyolefin (A), random alpha-olefin copolymer (B), and tackifier (C), optionally The product may be formed by (dry) blending, optionally, at least one additive, optionally, at least one filler, and optionally, at least one additional polymer (D_) powder, flakes, pellets, or a combination thereof, in the main hopper or side feeder of a shape extruder or film extruder, or an injection molding machine, or any other type of polymer processing apparatus known to those skilled in the art, and then by melt blending in the aforementioned processing apparatus. The processing apparatus may be the final stage of blending as part of the article manufacturing steps, such as an extruder used to melt and convey the composition before forming a sheet or pellet.

[0105] As used herein, the term “melt blending” includes the use of shear force, tensile force, compressive force, ultrasonic energy, electromagnetic energy, thermal energy, or a combination of at least one of the aforementioned forms of force or energy, and is carried out in a processing apparatus in which the aforementioned forces are applied by a single-screw, multi-screw, meshing co-rotating or counter-rotating screw, non-meshing co-rotating or counter-rotating screw, reciprocating screw, pinned screw, pinned barrel, roll, ram, helical rotor, or a combination of at least one of the aforementioned. Melt blending can be carried out in machinery such as single-screw or multi-screw extruders, Buss kneaders, Eirich mixers, Farrel continuous mixers, Haake mixers, Brabender internal mixers, helicones, Ross mixers, Banbury mixers, roll mills, injection molding machines, vacuum molding machines, blow molding machines, or a combination of at least one of the aforementioned machines. It is generally desirable to impart a specific energy of about 0.01 to about 10 kilowatt-hours / kilogram (kWh / kg) to the composition during melting. In another embodiment, the melt blending is carried out in a twin-screw extruder such as a Brabender co-rotating twin-screw extruder, and the screw temperature zone is set to approximately 110°C to 200°C for polyethylene-rich recycled polyethylene and approximately 140°C to 220°C for polypropylene-rich recycled polyolefins.

[0106] In at least one embodiment, a random alpha-olefin copolymer (B), a tackifier (C), or a combination of both is added in conjunction with a “masterbatch” approach, and the final random alpha-olefin copolymer and / or tackifier concentration is achieved by combining the recycled polyolefin with an appropriate amount of random alpha-olefin copolymer and / or tackifier pre-prepared at a higher additive concentration in a “carrier polymer” (masterbatch).

[0107] Such “carrier polymers” for the masterbatch may be ethylene polymers and / or propylene polymers, including but not limited to LDPE, LLDPE, HDPE, aPP, iPP, sPP, hPP, RCP and / or combinations thereof. The carrier polymer may be unused or recycled polyolefin. The carrier polymer may be recycled polyolefin (A) or identical to or different from the main component in recycled polyolefin (A).

[0108] As used herein, the term “identical” means equivalence in at least the origin (e.g., consumer waste), chemical structure (e.g., polyethylene), morphology (e.g., LLDPE), physical properties (e.g., density), and rheological properties (e.g., MFR). For example, both are derived from post-consumer waste, both are polypropylene-rich recycled polyolefins, both primarily contain HDPE, and both have a density of 0.950 g / cm³. 2 Two polymers having a density exceeding 3 g / 10 min and an MFR of 3 g / 10 min are considered identical.

[0109] As used herein, the term “different” may include, but is not limited to, differences in origin (e.g., consumer waste), chemical structure (e.g., polyethylene), morphology (e.g., LLDPE), physical properties (e.g., density), and rheological properties (e.g., MFR). For example, the use of polypropylene as a carrier polymer for a composition containing polyethylene-rich recycled polyolefin as recycled polyolefin (A), or the use of polyethylene having an MFR of 7.5 g / 10 min (ISO 1133, 190°C, 2.16 kg) as a carrier polymer for a composition containing polyethylene-rich recycled polyolefin having an MFR of 2.0 g / 10 min (ISO 1133, 190°C, 2.16 kg) as recycled polyolefin (A), is considered different from recycled polyolefin (A).

[0110] In at least one embodiment, the percentage of random alpha-olefin copolymer (B), tackifier (C), or a combination of both (B+C) is about 5 to about 70% by weight, based on the weight of the masterbatch composition. In other embodiments, the percentage of random alpha-olefin copolymer (B), tackifier (C), or a combination of both (B+C) is in the range of about 20 to about 60% by weight or about 40 to about 50% by weight. The masterbatch composition may contain additional additives, fillers, or polymers.

[0111] The masterbatch composition may be formed by any method known in the art. In one embodiment, the masterbatch composition is formed by first dry blending a powder, flakes, pellets, or a combination thereof using a tumble blender, for example, by first contacting a carrier polymer with at least one random alpha-olefin copolymer and / or tackifier (and any optional additives, fillers, or additional polymers) without completely mixing the carrier polymer and the random alpha-olefin copolymer and / or tackifier, and then melt-blending them in a mixer or any other type of mixing apparatus known to those skilled in the art.

[0112] In another embodiment, the masterbatch composition is formed by directly melt-blending a carrier polymer with at least one random alpha-olefin copolymer as powder, flakes, pellets, or a combination thereof, and / or a tackifier (and optionally selected additives, fillers, or additional polymers) in a mixer, a single-screw or twin-screw extruder, or other apparatus known to those skilled in the art; or by (dry) blending the powder, flakes, pellets, or a combination thereof of the carrier polymer with at least one random alpha-olefin copolymer and / or a tackifier (and optionally selected additives, fillers, or additional polymers) in a shape extruder or film extruder, or any other type of polymer processing apparatus known to those skilled in the art, in the main hopper or side feeder, and then melt-blending in the aforementioned processing apparatus.

[0113] The carrier polymer for use in the masterbatch can have MFRs in the range of approximately 0.5 to approximately 25, approximately 4 to approximately 25, approximately 5 to approximately 25, approximately 6 to approximately 25, approximately 7 to approximately 25, approximately 8 to approximately 25, approximately 9 to approximately 25, approximately 10 to approximately 25, approximately 11 to approximately 25, approximately 12 to approximately 25, approximately 13 to approximately 25, approximately 14 to approximately 25, and approximately 15 to approximately 25 g / 10 min (ISO1133, 190°C, 2.16 kg).

[0114] The carrier polymer for use in the masterbatch can have MFRs in the range of approximately 0.5 to approximately 25, approximately 4 to approximately 25, approximately 5 to approximately 25, approximately 6 to approximately 25, approximately 7 to approximately 25, approximately 8 to approximately 25, approximately 9 to approximately 25, approximately 10 to approximately 25, approximately 11 to approximately 25, approximately 12 to approximately 25, approximately 13 to approximately 25, approximately 14 to approximately 25, and approximately 15 to approximately 25 g / 10 min (ISO1133, 230°C, 2.16 kg).

[0115] In another embodiment, the masterbatch composition is formed by melt-blending a carrier polymer and a random alpha-olefin copolymer (B) and / or a tackifier (C) in a twin-screw extruder such as a Brabender co-rotating twin-screw extruder, with the screw temperature zone set to approximately 85°C to approximately 160°C for masterbatch compositions using unused LDPE with an MFR of approximately 2 to approximately 7.5 g / 10 min (ISO1133, 190°C, 2.16 kg), and approximately 120°C to approximately 185°C for masterbatch compositions using unused iPP with an MFR of approximately 2 to approximately 25 g / 10 min (ISO1133, 230°C, 2.16 kg).

[0116] The masterbatch composition may be in the form of pellets, granules, powders, or flakes, and may be additionally coated or powdered to improve processability. Examples of such coatings or powders include, but are not limited to, polyethylene wax, polypropylene wax, talc, or silica.

[0117] In at least one embodiment, the resulting polyolefin composition is in the form of pellets, granules, powders, or flakes suitable for further processing into articles containing such composition.

[0118] Additionally, other polymers, additives, or fillers may be included in the polyolefin composition, in one or more components of the composition, and / or in products formed from the composition, such as films, as desired.

[0119] Other polymers that may be included in the composition include terpolymers of ethylene vinyl acetate, ethylene methyl acrylate, ethylene ethyl acrylate, ethylene n-butyl acrylate, ethylene, ethyl acrylate and maleic anhydride, copolymers of acrylic acid, polymethyl methacrylate or any other polymers polymerizable by high-pressure free radical processes, LLDPE, LDPE, MDPE, HDPE, ethylene 1-hexene copolymer, copolymers and terpolymers of ethylene and alpha-olefin, copolymers and terpolymers of propylene and alpha-olefin, plastomers, metallocene-catalyzed polyolefins, maleic acid-modified polyolefins, maleic acid-modified polypropylene and polyethylene polymers, Polyvinyl chloride, polybutene-1, isotactic polybutene, acrylonitrile butadiene styrene (ABS) resin, MBS (methacrylate butadiene styrene) resin, ethylene propylene rubber (EPR), vulcanized EPR, EPDM (ethylene propylene diene monomer rubber), block copolymers, styrene-based block copolymers, maleic acid-modified styrene-based block copolymers, polyamides, polycarbonates, PET resins, crosslinked polyethylene, copolymers of ethylene and vinyl alcohol (EVOH), polymers of aromatic monomers (e.g., polystyrene), polyesters, polyacetals, polyvinylidene fluoride, polyethylene glycol, polyisobutylene, and / or combinations thereof may or may not be included.

[0120] In at least one embodiment, at least one of the “other polymers” can be used as a carrier polymer.

[0121] In at least one embodiment of the present invention, a polyolefin composition is provided comprising at least one "other polymer" as an "additional polymer." The terms "other polymer" and "additional polymer" are used interchangeably.

[0122] Some of these “other” or “additional” polymers have been found to surprisingly improve the impact performance of the polyolefin compositions of the present invention. At least one rheological, physical, and mechanical property, such as MFR, elongation, tensile strength, flexural strength, flexural modulus, and Young's modulus (E-modulus), is unexpectedly improved by the addition of the other polymers and / or a favorable balance of physical and rheological properties is provided. These “other” or “additional” polymers can be used as carriers in the masterbatch method, as additives in the masterbatch, can be dry-blended into the composition, or can be incorporated into the polyolefin composition by any process known to those skilled in the art. At least one "other" or "additional" polymer contained in the polyolefin composition is present in amounts of about 1% to about 60%, about 2% to about 60%, about 3% to about 60%, about 4% to about 60%, about 5% to about 60%, about 6% to about 60%, about 7% to about 60%, about 8% to about 60%, about 9% to about 60%, about 10% to about 60%, and about 11% of the polyolefin composition. It may also be %~approximately 60%, approximately 12%~approximately 60%, approximately 13%~approximately 60%, approximately 14%~approximately 60%, approximately 15%~approximately 60%, approximately 16%~approximately 60%, approximately 17%~approximately 60%, approximately 18%~approximately 60%, approximately 19%~approximately 60%, approximately 20%~approximately 60%, approximately 25%~approximately 60%, approximately 30%~approximately 60%, approximately 35%~approximately 60%, approximately 40%~approximately 60%, and approximately 45%~approximately 60%.

[0123] In at least one embodiment of the present invention, the at least one "other" or "additional" polymer contained in the polyolefin composition is approximately 1% to approximately 45% by weight of the polyolefin composition, approximately 2% to approximately 45% by weight, approximately 3% to approximately 45% by weight, approximately 4% to approximately 45% by weight, approximately 5% to approximately 45% by weight, approximately 6% to approximately 45% by weight, approximately 7% to approximately 45% by weight, approximately 8% to approximately 45% by weight, approximately 9% to approximately 45% by weight, and approximately 10% to approximately 4% by weight. It may also be 5% by weight, approximately 11% to 45% by weight, approximately 12% to 45% by weight, approximately 13% to 45% by weight, approximately 14% to 45% by weight, approximately 15% to 45% by weight, approximately 16% to 45% by weight, approximately 17% to 45% by weight, approximately 18% to 45% by weight, approximately 19% to 45% by weight, approximately 20% to 45% by weight, approximately 25% to 45% by weight, approximately 30% to 45% by weight, approximately 35% to 45% by weight, or approximately 40% to 45% by weight. In at least one embodiment of the present invention, the at least one "other" or "additional" polymer contained in the polyolefin composition is about 1% to about 25% by weight of the polyolefin composition, about 2% to about 25% by weight of the polyolefin composition, about 3% to about 25% by weight, about 4% to about 25% by weight, about 5% to about 25% by weight, about 6% to about 25% by weight, about 7% to about 25% by weight, about 8% to about It may also be 25% by weight, approximately 9% to approximately 25% by weight, approximately 10% to approximately 25% by weight, approximately 11% to approximately 25% by weight, approximately 12% to approximately 25% by weight, approximately 13% to approximately 25% by weight, approximately 14% to approximately 25% by weight, approximately 15% to approximately 25% by weight, approximately 16% to approximately 25% by weight, approximately 17% to approximately 25% by weight, approximately 18% to approximately 25% by weight, approximately 19% to approximately 25% by weight, or approximately 20% to approximately 25% by weight.

[0124] In one embodiment, at least one "other" or "additional" polymer that modifies the impact properties and / or other physical and / or rheological properties of the polyolefin composition may be prepared as a masterbatch comprising (A) about 40 to about 60% by weight of at least one random alpha-olefin copolymer, and B) about 40 to about 60% by weight of at least one "other" or "additional" polymer. Suitable "other" or "additional" polymers include, but are not limited to, ethylene-acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-butyl acrylate copolymers, terpolymers of ethylene, ethyl acrylate and maleic anhydride (available from SK Functional Polymers, Paris, France as LOTADER® 4700), MDPE, HDPE, LLDPE, LDPE, unused PP homopolymers, PP copolymers, ethylene-hexene, ethylene-octene copolymers, and ethylene-butene copolymers (available from Dow Chemical, USA as ENGAGE®, AFFINITY®, and AFFINITY® GA). Depending on the application and desired final properties, the level of masterbatch use can be varied between about 5% by weight and about 50% by weight of the polyolefin composition. In at least one aspect of this embodiment, the masterbatch usage level is about 2% to about 50% by weight of the polyolefin composition, about 3% to about 50% by weight, about 4% to about 50% by weight, about 5% to about 50% by weight, about 6% to about 50% by weight, about 7% to about 50% by weight, about 8% to about 50% by weight, about 9% to about 50% by weight, about 10% to about 50% by weight, about 11% to about 50% by weight, about 12% to It may be in the range of approximately 50% by weight, approximately 13% to approximately 50% by weight, approximately 14% to approximately 50% by weight, approximately 15% to approximately 50% by weight, approximately 16% to approximately 50% by weight, approximately 17% to approximately 50% by weight, approximately 18% to approximately 50% by weight, approximately 19% to approximately 50% by weight, approximately 20% to approximately 50% by weight, approximately 25% to approximately 50% by weight, approximately 30% to approximately 50% by weight, approximately 35% to approximately 50% by weight, and approximately 40% to approximately 50% by weight.

[0125] In at least one embodiment, a polyolefin composition is provided comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, C) at least one tackifier, and (D) about 2 to about 20% by weight of at least one additional polymer selected from the group consisting of ethylene vinyl acetate, ethylene methyl acrylate, ethylene ethyl acrylate, ethylene n-butyl acrylate, and terpolymers of ethylene, ethyl acrylate and maleic anhydride, wherein the polyolefin composition has a weight ratio of about 0.2 to about 5.0 random alpha-olefin copolymer to tackifier, the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier, and the polyolefin composition maintains acceptable mechanical properties. In at least one embodiment, a polyolefin composition is provided comprising (A) about 60 to about 96% by weight of at least one recycled polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, C) at least one tackifier, and (D) about 2 to about 20% by weight of at least one additional polymer, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, the polyolefin composition has an increase in melt flow rate of about 5 to about 600% compared to the same polyolefin composition without the random alpha-olefin copolymer, the additional polymer, and the tackifier, and the polyolefin composition maintains acceptable mechanical properties.

[0126] In at least one embodiment, a polyolefin composition comprising recycled polyolefin (A), at least one random alpha-olefin copolymer (B), at least one tackifier resin (C), and at least one additional polymer (D), wherein the at least one additional polymer is selected from the group consisting of linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, ethylene-hexene copolymer, ethylene-butene copolymer, and ethylene-octene copolymer, and the percentage of B+C+D is about 10 to about 60% by weight based on the weight of the total polyolefin composition. In other embodiments, the percentage of B+C+D is in the range of about 20 to 45% by weight and about 10 to 20% by weight. In other embodiments of the present invention, the weight ratio of B+C to D is about 0.2 to about 20, about 0.2 to about 5.0, and about 0.5 to about 2.0. In other embodiments, the weight ratio of B to C is 0.2 to 5.0. The polyolefin composition may have an increase in MFR of about 5% to 400% compared to the same polyolefin composition that does not contain at least one random alpha-olefin copolymer, a tackifier resin, and additional polymers. In at least one aspect of the above embodiments, the polyolefin composition has an increase in MFR of about 3% to about 400% and an increase in elongation at break of about 30% to about 150% compared to the same polyolefin composition that does not contain at least one random alpha-olefin copolymer, a tackifier resin, and additional polymers, and the polyolefin composition maintains acceptable mechanical properties.

[0127] In at least one embodiment, a polyolefin composition comprising recycled polyolefin (A), at least one random alpha-olefin copolymer (B), at least one tackifier resin (C), and at least one additional polymer (D), wherein the at least one additional polymer is selected from the group consisting of linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, ethylene-hexene copolymer, ethylene-butene copolymer, and ethylene-octene copolymer, and the percentage of B+C+D is in the range of about 10 to about 60% by weight, about 20 to about 45%, or about 10 to about 20% by weight, based on the weight of the total polyolefin composition. The weight ratio of B+C to D is approximately 0.2 to approximately 20, approximately 0.2 to approximately 5.0, or approximately 0.5 to approximately 2.0, the weight ratio of B to C is 0.2 to 5.0, the polyolefin composition has an increase in MFR of approximately 5% to 400% compared to the same polyolefin composition without at least one random alpha-olefin copolymer, tackifier resin and additional polymers, the polyolefin composition has an increase in elongation at break of approximately 30% to approximately 150% compared to the same polyolefin composition without at least one random alpha-olefin copolymer, tackifier resin and additional polymers, and the polyolefin composition maintains acceptable mechanical properties. Acceptable mechanical properties are defined herein.

[0128] In at least one embodiment, a polyolefin composition comprising polyethylene-rich recycled polyolefin (A), at least one random alpha-olefin copolymer (B), at least one tackifier resin (C), and at least one additional polymer (D). The additional polymer may be, but is not limited to, linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, ethylene-hexene copolymer, ethylene-butene copolymer, or ethylene-octene copolymer. The polyolefin composition may be prepared such that the percentage of B+C+D is about 10 to about 60% by weight or about 20 to about 45% by weight, based on the weight of the total polyolefin composition. The weight ratio of B to C in the polyolefin composition may be 0.2 to 5.0. Furthermore, in certain embodiments, the polyolefin composition has an increase of about 100% to 250% in MFR and an increase of about 100% to 600% in elongation at break compared to the same polyolefin composition that does not contain at least one random alpha-olefin copolymer, a tackifier resin, and additional polymers, while the polyolefin maintains acceptable mechanical properties.

[0129] In at least one embodiment, the polyolefin composition comprises polyethylene-rich recycled polyolefin (A), at least one random alpha-olefin copolymer (B), at least one tackifier resin (C), and at least one additional polymer (D), the additional polymer being selected from linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, ethylene-hexene copolymer, ethylene-butene copolymer, or ethylene-octene copolymer, the percentage of B+C+D being about 10 to about 60% by weight or about 20 to about 45% by weight based on the weight of the total polyolefin composition, the weight ratio of B to C in the polyolefin composition being about 0.2 to 5.0, the polyolefin composition having an increase in MFR of about 100% to 250% and an increase in elongation at break of about 100% to about 600% compared to the same polyolefin composition without at least one random alpha-olefin copolymer, tackifier resin, and additional polymer, and the polyolefin maintains acceptable mechanical properties.

[0130] In at least one embodiment of the present invention, a polyolefin composition is provided comprising a polypropylene-rich recycled polyolefin (A), at least one random alpha-olefin copolymer (B), at least one tackifier resin (C), and at least one additional polymer (D), wherein the percentage of B+C+D may range from about 10 to about 60% by weight or about 20 to about 45% by weight, based on the weight of the total polyolefin composition. The weight ratio of B to C may be 0.2 to 5.0. The polyolefin composition may have an increase of about 3% to about 60% in MFR compared to the same polyolefin composition without at least one random alpha-olefin copolymer, tackifier resin, and additional polymer, while maintaining acceptable mechanical properties. In some aspects of this embodiment, the polyolefin composition also has an increase of about 30% to about 150% in elongation at break. In other aspects of this embodiment, the polyolefin composition also has an increase of about 40% in flexural strength, while maintaining acceptable mechanical properties.

[0131] In at least one embodiment of the present invention, a polyolefin composition is provided comprising a polypropylene-rich recycled polyolefin (A), at least one random alpha-olefin copolymer (B), at least one tackifier resin (C), and at least one additional polymer (D), wherein the percentage of B+C+D is about 10 to about 60% by weight or about 20 to about 45% by weight based on the weight of the total polyolefin composition, and the weight ratio of B to C is 0.2 to 5.0, wherein the polyolefin composition has an increase of about 3% to about 60% in MFR compared to the same polyolefin composition without at least one random alpha-olefin copolymer, tackifier resin, and additional polymer, and the polyolefin composition also has an increase of about 40% in flexural strength while maintaining acceptable mechanical properties. In some aspects of this embodiment, the polyolefin composition also has an increase of about 30% to about 150% in elongation at break.

[0132] In at least one embodiment of the present invention, a random alpha-olefin copolymer (B) having a recycled polyolefin (A), a glass transition temperature of -10°C or lower (ASTM D 3418-15) and a nominal molecular weight of 25,000 g / mol or lower (ISO 16014), and a glass transition temperature of 45°C or higher (ASTM D 3418-15). A polyolefin composition is provided comprising a tackifier (C), (C) and an additional polymer (D), wherein the additional polymer is not limited to linear low-density polyethylene, medium-density polyethylene, ethylene methyl acrylate copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, or ethylene-octene copolymer, the percentage of B+C+D is about 5 to about 30% by weight or about 10 to about 20% by weight based on the weight of the total polyolefin composition, the weight ratio of B+C to D is about 0.2 to 20.0, about 0.2 to about 5.0, or about 0.5 to 2.0, and the weight ratio of B to C is about 0.2 to 5.0, the polyolefin composition has an increase in MFR of about 5 to 400% compared to the same polyolefin composition without random alpha-olefin copolymer, tackifier and additional polymer, and the polyolefin composition maintains acceptable mechanical properties.

[0133] In at least one embodiment of the present invention, a random alpha-olefin copolymer (B) having a recycled polyolefin (A), a glass transition temperature of -10°C or lower (ASTM D 3418-15) and a nominal molecular weight of 10,000 g / mol or lower (ISO 16014), and a glass transition temperature of 45°C or higher (ASTM D 3418-15). A polyolefin composition is provided comprising a tackifier (C), (C) and an additional polymer (D), wherein the additional polymer is not limited to linear low-density polyethylene, medium-density polyethylene, ethylene methyl acrylate copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, or ethylene-octene copolymer, the percentage of B+C+D is about 5 to about 30% by weight or about 10 to about 20% by weight based on the weight of the total polyolefin composition, the weight ratio of B+C to D is about 0.2 to 20.0, about 0.2 to about 5.0, or about 0.5 to 2.0, and the weight ratio of B to C is about 0.2 to 5.0, the polyolefin composition has an increase in MFR of about 5 to 400% compared to the same polyolefin composition without random alpha-olefin copolymer, tackifier and additional polymer, and the polyolefin composition maintains acceptable mechanical properties.

[0134] In at least one embodiment of the present invention, a polyolefin composition is provided comprising recycled polyolefin (A), a random alpha-olefin copolymer (B), a tackifier (C), and an additional polymer (D), wherein the additional polymer may be, but is not limited, linear low-density polyethylene, medium-density polyethylene, ethylene methyl acrylate copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, or ethylene-octene copolymer, the percentage of B+C+D being about 5 to about 30% by weight or about 10 to about 20% by weight based on the weight of the total polyolefin composition, the weight ratio of B+C to D being about 0.2 to 20.0, about 0.2 to about 5.0, or about 0.5 to 2.0, and the weight ratio of B to C being about 0.2 to 5.0, wherein the polyolefin composition has an increase in MFR of about 5 to 400% compared to the same polyolefin composition without the random alpha-olefin copolymer, tackifier, and additional polymer, and the polyolefin composition maintains acceptable mechanical properties.

[0135] In certain aspects of this embodiment, the additional polymer (D) is maleic acid-modified polyethylene or polypropylene, the percentage of D is about 1–5% by weight or about 1–3% by weight, the weight ratio of B+C to D is about 2–20 or about 5–10, the polyolefin composition has an increase of about 5–100% in MFR, exhibits improved compatibilization with impurities present in the recycled polyolefin (A), and the polyolefin composition maintains acceptable mechanical properties.

[0136] In another specific aspect of this embodiment, the additional polymer (D) is linear low-density polyethylene (LLDPE), the recycled polyolefin is polypropylene-rich recycled polyolefin, the percentage of D is about 5 to about 30% by weight, about 10 to about 20% by weight, the weight ratio of B+C to D is about 0.2 to about 2, or about 0.3 to about 1, the polyolefin composition has about 5 to 100% increase in MFR and about 5 to 200% increase in notched impact strength compared to the same polyolefin composition without random alpha-olefin copolymer, tackifier and additional polymer, and the polyolefin composition maintains acceptable mechanical properties.

[0137] In yet another specific aspect of this embodiment, an additional polymer is used as a carrier polymer for the masterbatch, and a polyolefin composition is prepared in which the B+C percentage is about 5 to about 70% by weight, or about 40 to about 60% by weight, based on the weight of the masterbatch. The masterbatch percentage may range from about 5 to about 40% by weight, or about 10 to about 20% by weight, of the total polyolefin composition, and the polyolefin composition has an increase of about 5 to 100% MFR compared to the same polyolefin composition without the masterbatch, and the polyolefin composition maintains acceptable mechanical properties.

[0138] In at least one embodiment, a polyolefin composition is provided comprising a recycled polyolefin (A), a random alpha-olefin copolymer (B), a tackifier (C), and an additional polymer (D), wherein the alpha-olefin copolymer (B) and the tackifier (C) are initially prepared as a masterbatch using a carrier polymer. The carrier polymer may be unused or recycled polyolefin and may be identical to or different from the recycled polyolefin (A) or the main component in the recycled polyolefin (A) or the additional polymer (D). The percentage of B+C is about 5 to about 70% by weight or about 40 to about 60% by weight, based on the weight of the masterbatch, and the weight ratio of B to C is 0.2 to 5.0. The percentage of the masterbatch may be in the range of about 5 to about 40% or 10 to 20% of the total polyolefin composition. The masterbatch to additional polymer (D) ratio may range from about 0.2 to about 20, or about 0.2 to about 5.0, or about 0.5 to about 2.0, and the polyolefin composition has an increase in MFR of about 5 to 400% compared to the same polyolefin composition without random alpha-olefin copolymers, tackifiers, and additional polymers, and the polyolefin composition maintains acceptable mechanical properties.

[0139] In at least one embodiment, a polyolefin composition is provided comprising a recycled polyolefin (A), a random alpha-olefin copolymer (B) having a glass transition temperature of -10°C or lower (ASTM D 3418-15) and a nominal molecular weight of 25,000 g / mol or lower (ISO 16014), a tackifier (C) having a glass transition temperature of 45°C or higher (ASTM D 3418-15), and an additional polymer (D), wherein the alpha-olefin copolymer (B) and tackifier (C) are initially prepared as a masterbatch using a carrier polymer. The carrier polymer may be unused or recycled polyolefin and may be identical to or different from the recycled polyolefin (A) or the main component in the recycled polyolefin (A) or the additional polymer (D). The percentage of B+C is about 5 to about 70 by weight or about 40 to about 60% based on the weight of the masterbatch, and the weight ratio of B to C is 0.2 to 5.0. The percentage of the masterbatch may range from about 5 to about 40% or 10 to 20% of the total polyolefin composition. The masterbatch to additional polymer (D) ratio may range from about 0.2 to about 20, or about 0.2 to about 5.0, or about 0.5 to about 2.0, and the polyolefin composition has an increase in MFR of about 5 to about 400% compared to the same polyolefin composition without random alpha-olefin copolymers, tackifiers and additional polymers, and the polyolefin composition maintains acceptable mechanical properties.

[0140] In another aspect of this embodiment, the additional polymer may be, but is not limited to, linear low-density polyethylene, medium-density polyethylene, ethylene methyl acrylate copolymer, ethylene hexene copolymer, ethylene butene copolymer, or ethylene octen copolymer.

[0141] Surprisingly, the test standard deviation of the polyolefin composition was found to be significantly lower than that of the unmodified recycled polyolefin sample. This significant reduction in test variability indicates that the polyolefin composition has more consistent composition and quality than the unmodified recycled polyolefin. This is industrially advantageous when producing consistent products from recycled polyolefins.

[0142] Such additives that may be included in a polyolefin composition include antioxidants (AOs) (e.g., sterically hindered phenols such as IRGANOX® 1010 or IRGANOX® 1076 by BASF, phosphorus-based AOs such as IRGAFOS® 168 by BASF, sulfur-based AOs such as Irganox PS-802 FL® by BASF, nitrogen-based AOs such as 4,4'-bis(1,1'-dimethylbenzyl)diphenylamine or AO blends), antacids (e.g., calcium stearate, sodium stearate, zinc stearate, magnesium and zinc oxide, synthetic hydrotalcite, lactate and lactylate), anti-tack additives, plasticizers, tackifiers (e.g., polybutene, terpene resins, aliphatic and aromatic hydrocarbon resins, alkali metal and glycerol stearates, and hydrogenated rosin), UV stabilizers (e.g., bis-(2'2'6'6-tetramethyl-4-piperidyl)-sebacate), and heat-resistant additives. Stabilizers, nucleating agents (e.g., sodium benzoate, 1,3:2,4-bis(3,4-dimethylobenzylideno)sorbitol), antiblocking agents (e.g., diatomaceous earth; synthetic silica; silicates such as kaolin, sodium aluminum silicate, calcined kaolin, aluminum silicate or calcium silicate; synthetic zeolites), crosslinking agents, release agents, antistatic agents (e.g., glycerol esters, ethoxylated amines, ethoxylated amides), antimicrobial agents, biocides, foaming agents, leavening agents, clarifying agents, flame retardants, catalysts, pigments, colorants, dyes, waxes, or combinations thereof may be, but are not limited to, these additives. Typically, these additives may be included in amounts of about 100 to about 2000 ppm for each individual additive.

[0143] Examples of fillers that may be included in the composition include, but are not limited to, coal, fly ash, calcium carbonate, barium sulfate, carbon black, metal oxides, inorganic materials, natural materials, alumina trihydrate, magnesium hydroxide, bauxite, talc, mica, barite, kaolin, silica, post-consumer glass or post-industrial glass, sawdust, synthetic and natural fibers, or any combination thereof. The fillers may be organic, inorganic, or a combination of both (e.g., in different forms).

[0144] Other polymers, additives, and fillers may be added in amounts known to those skilled in the art. For example, the amount of additives in the polyolefin composition may be less than 10% by weight, less than 5% by weight, less than 1% by weight, and less than 0.3% by weight, based on the weight of the polyolefin composition. In other embodiments of the present invention, the amount of filler in the polyolefin composition may be about 5 to about 85% by weight, about 5 to about 75% by weight, about 5 to about 65% by weight, about 5 to about 55% by weight, about 5 to about 45% by weight, about 5 to about 35% by weight, about 5 to about 25% by weight, and about 5 to about 20% by weight, based on the weight of the polyolefin composition.

[0145] Viscosity breaking process for producing polyolefin compositions In another embodiment of the present invention, a process for producing a polyolefin composition is provided, comprising: 1) extruding at least one recycled polyethylene-rich polyolefin in the presence of at least one radical initiator to produce an extruded bis-breaking recycled polyethylene-rich polyolefin; and 2) melt-blending (A) about 60 to about 96% by weight of the bis-breaking recycled polyethylene-rich polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, C) optionally about 2 to about 20% by weight of at least one tackifier, and D) optionally at least one additional polymer, wherein the extruded bis-breaking polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, and the extruded bis-breaking polyolefin composition has an increase in melt flow rate of about 5 to about 1500% compared to the recycled polyolefin.

[0146] Recycled polyethylene-rich polyolefins, random alpha-olefin copolymers, tackifiers, and additional or other polymers are described herein first.

[0147] The present invention relates to a novel process for bis-breaking and blending recycled polyolefins to form a polyolefin composition. Bis-breaking is defined as subjecting a polyolefin to chain severance, which reduces the molecular weight and increases the melt flow rate. In one embodiment, the process employs a single extrusion step that results in a significant increase in the MFR of the starting recycled polyolefin without any crosslinking.

[0148] Starting materials for the bis-breaking process to produce polyolefin compositions In one embodiment of the present invention, the process uses a starting polyethylene that is a post-consumer or post-industrial polyethylene-rich polyolefin stream having a density of about 910 to about 1050 kg / m3, or an ethylene plastomer or elastomer having a density of about 855 to about 960 kg / m3. The ethylene elastomer may have a density of about 855 to about 950 kg / m3, and the ethylene plastomer may have a density of about 880 to about 950 kg / m3.

[0149] Extrusion conditions for the screw breaking process To increase the melt flow rate of the starting recycled polyethylene-rich polyolefin in the bis-breaking process, the recycled polyethylene-rich polyolefin is extruded under specific conditions using a specific radical initiator. In one embodiment of the present invention, the extrusion process is carried out using at least one of high temperature, high shear, and / or high speed. Furthermore, the desired increase in MFR can be achieved using a single extrusion step. Many prior art processes require complex multiple extrusions. In the present invention, a significant increase in MFR can be achieved using a single extrusion.

[0150] Therefore, the extruder may be a single-screw extruder, a twin-screw extruder such as a co-rotating twin-screw extruder or a counter-rotating twin-screw extruder, or a multi-screw extruder such as a ring extruder. Suitable extruders include single-screw extruders and twin-screw extruders. In one embodiment of the present invention, the extruder is a co-rotating twin-screw extruder.

[0151] Suitable extruders are typically 125–2540 cm, 510–1270 cm, or 635–1020 cm in length. The residence time of the polymer feed material in the extruder is typically about 30 seconds to 5 minutes, or about 30 seconds to 3 minutes.

[0152] Extruders typically have multiple heating zones. It should be noted that a considerable amount of heat is often generated from shear heating during the extrusion process. Therefore, the temperature of the polymer molten in the extruder may be substantially higher than the temperature set in the heating zones in the screw barrel, and substantially higher than the actual zone temperature readings in the extruder. Furthermore, the actual zone temperature readings at different stages of the extruder may also be higher than the temperatures set in the heating zones. The temperatures referred to herein are those set in the heating zones.

[0153] Such extruders are well known in the art and are supplied, for example, by Coperion, Japan Steel Works, Krauss Maffei Berstorff, or Leisteritz.

[0154] In one embodiment, the extrusion is high-temperature extrusion. High temperature means that the maximum barrel temperature is set to a minimum of 250°C or a minimum of 300°C. In other embodiments, the maximum barrel temperature is at least 310°C, at least 325°C, at least 340°C or at least 350°C. The upper limit of the maximum barrel zone temperature extruder may be 400°C.

[0155] This can be converted to a melting temperature of the polymer molten exiting the die of at least 240°C, at least 290°C, at least 310°C, at least 320°C, at least 330°C, or at least 340°C. The upper limit of the melting temperature exiting the die may be 390°C.

[0156] In another embodiment of the present invention, the extruder has 10 to 14 zones, for example, 12 zones. In another embodiment, a high extrusion temperature is applied by zone 3. The maximum extrusion temperature can be applied by zone 3 and maintained across the remaining zones of the extruder.

[0157] The die plate temperature may be approximately 120°C to approximately 180°C. In another embodiment, the temperature profile can be set as follows: Zone 1 is below 80°C, Zone 2 is 80°C to 120°C, and Zones 3 to 12 are 250°C or higher. In another embodiment, the temperature profile can be set as follows: Zone 1 is 20°C, Zone 2 is 100°C, Zones 3 to 12 are 350°C, and the die plate is 150°C.

[0158] While we do not wish to be limited by theory, the inventors believe that higher temperatures lead to an increase in MFR, and therefore a decrease in molecular weight.

[0159] In another embodiment of the present invention, the extruder can be operated at a high screw speed. A high screw speed means that the extruder screw rotates at a speed of at least 300 rpm, at least 350 rpm, or at least 400 rpm. Much higher screw speeds, such as 600 rpm or more, 800 rpm or more, or 1000 rpm or more, can also be used. The upper limit of the screw speed is governed by the extruder used, but may be as high as 1300 rpm. The screw speed may be in the range of 450 to 1200 rpm. It is preferable that the screw speed remains constant throughout the entire process. Although we do not wish to be limited by theory, the inventors believe that higher screw speeds result in an increase in MFR and therefore a decrease in molecular weight.

[0160] Throughput is also related to the increase in MFR. Since the polymer is subjected to less screw-breaking conditions within the extruder, higher throughput results in a lower increase in MFR. Therefore, while high screw speeds are often desirable, it is also desirable to keep throughput values ​​low. Suitable throughputs in industrial extruders can be 5–40 kg / hour or 10–20 kg / hour. Lower throughput results in higher MFR.

[0161] The screw speed is also related to the residence time in the extruder. A faster screw speed means a shorter residence time. The residence time of the process of the present invention in the extruder may be in the range of 30 seconds to 1.5 minutes or 35 seconds to 70 seconds.

[0162] In this regard, the specific energy input to the process should also be considered. Specific energy input (SEI) is the amount of energy supplied to the extruder motor per kilogram of polymer material. Higher screw speeds mean more power to the motor. Higher output requires more power from the motor. A high SEI can achieve a high final MFR. The correlation between SEI and MFR is essentially linear.

[0163] The energy input to the extruder motor can be measured from the extruder itself. It is the derivable product from the extruder. It will be understood that the SEI value depends on the size and properties of the extruder used. Therefore, the SEI can be at least 0.2 kWh / kg, or at least 0.4 kWh / kg, measured using Coperion ZSK32.

[0164] The process of the present invention can also utilize high shear. The high shear effect may originate from one or more kneader 90° screw elements that can be positioned in the mixing zone of the extruder. The extruder screw elements and screw configuration can be designed to promote a strong shear effect with optimized melt mixing.

[0165] The extruded bis-breaked polyethylene-rich recycled polyolefin exiting the extruder die is collected in a sealed container and held in a liquid state for transport to the next step or to the extruder, and can be modified with additives and / or fillers at a lower temperature before pelletizing. In one embodiment of the present invention, the extruded bis-breaked polyethylene-rich recycled polyolefin exiting the extruder die can be pelletized using conventional pelletizing techniques. Thus, a further aspect of the present invention is that the extruded bis-breaked recycled polyethylene-rich polyolefin exiting the extruder is pelletized.

[0166] Extruder for screw breaking process More specifically, an extruder typically includes a feed zone, a melting zone, a mixing zone, and a die zone. Furthermore, the molten material pressed through the die is typically solidified and cut into pellets by a pelletizer. Extruders typically have a length-to-diameter ratio (L / D) of about 6:1 to about 65:1, or about 8:1 to 60:1. As is well known in the art, co-rotating twin-screw extruders usually have a larger L / D than counter-rotating twin-screw extruders. Extruders may have one or more discharge or vent ports for removing gaseous components from the extruder.

[0167] Such discharge ports should be located downstream enough to allow sufficient reaction time between the initiator and the recycled polyolefin. Preferably, the discharge ports can be located within the downstream end of the melting zone or within the mixing zone.

[0168] To help remove volatile components from the polymer molten material, a release agent such as water, steam, or nitrogen is preferably added to the extruder. When used, such a release agent is added upstream of the discharge port, or, if there are multiple discharge ports, upstream of the furthest downstream discharge port.

[0169] The extruder may also have one or more supply ports for supplying further components, such as polymers and additives, to the extruder. The location of such additional supply ports depends on the type of material being added through the ports.

[0170] Supply zone for the screw breaking process Recycled polyethylene-rich polyolefin is introduced into the extruder through a feed zone. The feed zone leads the recycled polyethylene-rich polyolefin to the melting zone. Typically, the feed zone consists of a feed hopper and a connecting pipe that connects the hopper to the melting zone. The polymer usually flows through the feed zone under the influence of gravity, i.e., generally downwards.

[0171] The residence time of recycled polyethylene-rich polyolefins (and other components) in the supply zone is typically short, usually 30 seconds or less, more often 20 seconds or less, for example, 10 seconds or less. Typically, the residence time is at least 0.1 seconds or at least 1 second.

[0172] Molten zone for the screw breaking process Recycled polyethylene-rich polyolefin is sent from the supply zone to the melting zone. In the melting zone, the recycled polyethylene-rich polyolefin is melted. The recycled polyethylene-rich polyolefin is transported by the drag force generated by the rotating screw. The temperature then rises along the length of the screw due to the dissipation of frictional heat, reaching a level above the melting temperature of the polymer. This causes the solid particles to begin melting.

[0173] The screw in the melting zone is preferably designed so that the screw in the melting zone is completely filled. This allows the solid particles to form a compact bed in the melting zone. This occurs when sufficient pressure is generated within the screw channel and the screw channel is completely filled. Typically, the screw in the melting zone includes a conveying element with virtually no backflow. However, to achieve a compact bed, some barriers or back-mixing elements may need to be installed in suitable locations, for example, close to the downstream end of the melting zone. Screw designs for obtaining a compact particle bed are well known in the extruder industry. Due to frictional heat, the temperature rises along the length of the screw, and the recycled polyolefin begins to melt.

[0174] Mixing zone for the screw breaking process After the melting zone, the recycled polyethylene-rich polyolefin is sent to the mixing zone. The screw in the mixing zone typically includes one or more mixing sections containing screw elements that provide some degree of backflow. In the mixing zone, the polymer melts are mixed to achieve a homogeneous mixture. The mixing zone may also include additional elements such as a throttle valve or a gear pump.

[0175] The temperature in the mixing zone must be higher than the melting temperature of the recycled polyolefin. Furthermore, the temperature must be higher than the decomposition temperature of the initiator. The temperature must be lower than the decomposition temperature of the recycled polyolefin.

[0176] The overall average residence time in the combined molten and mixed zones of the extruder may be at least about 25 seconds and / or at least about 30 seconds. Typically, the average residence time does not exceed 60 seconds or 55 seconds. Good results were obtained when the average residence time was in the range of 30 to 45 seconds.

[0177] As mentioned above, it is desirable to remove gaseous material from the extruder through one or more discharge ports, sometimes called vent ports. It is possible to use two or more discharge ports. For example, there may be two ports: an upstream port for rough degassing and a downstream port for removing residual volatile substances. Such a configuration is advantageous when a large amount of gaseous material is present in the extruder.

[0178] Vent ports are preferably located in the mixing zone. However, they may also be located at the downstream end of the melting zone. In particular, when multiple vent ports are present, it may be advantageous to have the upstream port in the melting zone and subsequent ports in the mixing zone. It is also possible to add release agents such as water, steam, CO2, or N2 to the extruder.

[0179] When used, such release agents are introduced upstream of the vent port, or, if multiple vent ports exist, upstream of the furthest downstream vent port and downstream of the upstream vent ports. Typically, the release agent is introduced into the mixing zone or at the downstream end of the melting zone.

[0180] The die zone typically includes a die plate, sometimes called a breaker plate, which is a thick metal disc with multiple holes. The holes are parallel to the screw axis. The molten recycled polyolefin is pressed through the die plate. Thus, the molten recycled polyolefin forms numerous strands. The strands are then passed to the pelletizer. The function of the die plate is to prevent the spiral motion of the recycled polyolefin molten material and to force it to flow in one direction. The die zone may also typically include one or more screens supported by the die plate. The screens are used to remove impurities from the recycled polyolefin molten material and to remove gels from the polymer. The gels are typically non-dispersible high molecular weight polymers, such as crosslinked polymers.

[0181] Radical initiator for bis-breaking process to produce polyolefin compositions The radical initiator used in the process of the present invention is any known in the art. In one embodiment, the radical initiator decomposes at a high temperature, i.e., at least 200°C. This means that the self-accelerating decomposition temperature (SADT) of the initiator of the present invention is preferably at least 200°C. Thus, the initiator is stable up to this temperature. Therefore, the initiator generally does not begin to decompose until the polymer molten material has passed through the extruder and possibly reached zone 3.

[0182] If an initiator that decomposes at a lower temperature is used, the initiator decomposes too quickly or too rapidly in the process, and the required increase in MFR is not achieved. For example, peroxides lose their activity very rapidly and become unsuitable for use in the process of the present invention. Alternatively, the initiator is not a peroxide. Peroxide initiators generally decompose at temperatures too low to be useful in the present invention.

[0183] In the process of the present invention, the radical initiator may be present in an amount of at least 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, or 1.3% by weight and / or 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, or 1.4% by weight or less, based on the amount of recycled polyolefin present. In another embodiment of the present invention, the radical initiator is used in the process of the present invention in amounts of about 0.01 to about 2.0% by weight, about 0.02 to about 2.0% by weight, about 0.03 to about 2.0% by weight, about 0.04 to about 2.0% by weight, about 0.04 to about 2.0% by weight, about 0.05 to about 2.0% by weight, about 0.06 to about 2.0% by weight, about 0.07 to about 2.0% by weight, about 0.08 to about 2.0% by weight, about 0.09 to about 2.0% by weight, and about 0. It may exist in amounts of 1 to approximately 2.0% by weight, approximately 0.2 to approximately 2.0% by weight, approximately 0.3 to approximately 2.0% by weight, approximately 0.4 to approximately 2.0% by weight, approximately 0.5 to approximately 2.0% by weight, approximately 0.6 to approximately 2.0% by weight, approximately 0.7 to approximately 2.0% by weight, approximately 0.8 to approximately 2.0% by weight, approximately 0.9 to approximately 2.0% by weight, approximately 1.0 to approximately 2.0% by weight, approximately 1.1 to approximately 2.0% by weight, approximately 1.2 to approximately 2.0% by weight, approximately 1.3 to approximately 2.0% by weight, approximately 1.4 to approximately 2.0% by weight, or approximately 1.5 to approximately 2.0% by weight. In other embodiments, the amount of radical initiator is in the range of about 0.1 to about 1% by weight, about 0.2 to about 1.0% by weight, about 0.3 to about 1.0% by weight, about 0.4 to about 1.0% by weight, about 0.5 to about 1.0% by weight, or about 0.6 to about 1.0% by weight, based on the amount of recycled polyolefin present. Therefore, when using 100 g of recycled polyolefin, 0.1 to 2.0 g of radical initiator may be present. The above amounts of radical initiator are the total amount added. It will be understood that the radical initiator may be added in one batch or in separate batches in different parts of the extruder.

[0184] However, in one embodiment, all initiators are added at the start of the process. Process start means that the radical initiator is added to the first zone of the extruder along with the recycled polyolefin.

[0185] In one embodiment of the present invention, a portion of the radical initiator is added at the start of the extrusion process, and a portion of the radical initiator is added later in the process. In this embodiment, the amount added at the start of the process corresponds to 30-70% by weight, 40-60% by weight, or about 50% by weight of the total radical initiator added. The amount added after the start of the process may correspond to 30-70% by weight, 40-60% by weight, or 50% by weight of the total radical initiator added.

[0186] Radical initiators added later in the process can be added to any later zone in the extrusion process, for example, the fourth, fifth, sixth, or seventh zone, particularly the sixth zone. In one embodiment of the present invention, the extruder has 12 zones.

[0187] In another embodiment of the present invention, the starting recycled polyolefin is fed into the main hopper of the extruder. The radical initiator can be fed into the first zone of the extruder all at once, or into both the first and sixth zones simultaneously, based on half of its amount.

[0188] The amount of initiator added can be used to control the MFR of the final extruded bis-breaking recycled polyethylene-rich polyolefin. Higher amounts of initiator tend to result in higher MFR values.

[0189] The radical initiator used in the present invention is preferably not a peroxide. The initiator is at least one compound (E) that can be thermally decomposed into a carbon-based free radical by breaking at least one single bond, such as a carbon-carbon single bond or a carbon-hydrogen bond. The carbon-based free radical may have formula (I) or (II).

[0190] [ka]

[0191] In formula (I), each of R1, R2, and R3 can be independently selected from hydrogen, a substituted or unsubstituted linear, branched, or cyclic saturated or monounsaturated hydrocarbon having 1 to 12 carbon atoms, a substituted or unsubstituted aromatic hydrocarbon having 6 to 12 carbon atoms, or a carboxylate group COOX (where X is a C1-C6 alkyl group), and at least one of R1, R2, and R3 is a substituted or unsubstituted aromatic hydrocarbon having 6 to 12 carbon atoms.

[0192] In formula (II), R4 and R6 are independently selected from the group consisting of hydrogen, substituted and unsubstituted linear, branched, and cyclic hydrocarbons having 1 to 12 carbon atoms, and substituted and unsubstituted aromatic hydrocarbons having 6 to 12 carbon atoms, and R5 is selected from the group consisting of substituted and unsubstituted linear, branched, and cyclic hydrocarbons having 1 to 12 carbon atoms, and substituted and unsubstituted aromatic hydrocarbons having 6 to 12 carbon atoms, and at least one of R4, R5, and R6 is a substituted or unsubstituted aromatic hydrocarbon having 6 to 12 carbon atoms.

[0193] Preferred carbon-based free radicals of formula (I) or (II) are known, for example, from Chemicals Reviews, 2014, 114, p5013, Figure 1, radicals R1 to R61, and are incorporated herein by reference to the extent that they are not inconsistent with the description herein. Each of R1 and R3 can be independently selected from the group consisting of hydrogen, substituted and unsubstituted linear, branched and cyclic hydrocarbons having 1 to 12 carbon atoms, and substituted and unsubstituted aromatic hydrocarbons having 6 to 12 carbon atoms, and R2 can be selected from the group consisting of substituted and unsubstituted linear, branched and cyclic hydrocarbons having 1 to 12 carbon atoms, and substituted and unsubstituted aromatic hydrocarbons having 6 to 12 carbon atoms.

[0194] As described above, at least one of groups R1, R2 and R3 or R4, R5 and R6 is a substituted or unsubstituted aromatic hydrocarbon having 6 to 12 carbon atoms. Therefore, a suitable carbon-based free radical of formula (I) or formula (II) in the present invention is preferably generated from one or more compounds (E) of formula (III), where each of R1, R3, R4 and R6 is independently selected from the group consisting of hydrogen, substituted and unsubstituted linear, branched and cyclic hydrocarbons having 1 to 12 carbon atoms, and substituted and unsubstituted aromatic hydrocarbons having 6 to 12 carbon atoms; each of R2 and R5 is independently selected from the group consisting of substituted and unsubstituted linear, branched and cyclic hydrocarbons having 1 to 12 carbon atoms, and substituted and unsubstituted aromatic hydrocarbons having 6 to 12 carbon atoms; and at least one of R1, R2, R3, R4, R5 and R6 is a substituted or unsubstituted aromatic hydrocarbon having 6 to 12 carbon atoms.

[0195] [ka]

[0196] Compound (E) of formula (III) can have symmetric and asymmetric structures. Each of R2 and R5 can be independently selected from substituted or unsubstituted aromatic hydrocarbons having 6 to 12 carbon atoms, or from the group consisting of substituted and unsubstituted aryl groups having 6 to 10 carbon atoms, and each of R1, R3, R4 and R6 can be independently selected from the group consisting of hydrogen and C1-C6 alkyl groups.

[0197] In another embodiment, the initiator (E) has formula (IV),

[0198] [ka] In the formula, each of R7, R8, R9, and R10 is independently selected from the group consisting of hydrogen atoms, C1-6 alkyl groups, C1-2 alkoxy groups, nitrile groups, and halogen atoms, and each of R1, R3, R4, and R6 is independently selected from the group consisting of hydrogen and C1-6 alkyl groups.

[0199] In yet another embodiment, initiator (E) is 2,3-dimethyl-2,3-diphenylbutane, 2,3-dipropyl-2,3-diphenylbutane, 2,3-dibutyl-2,3-diphenylbutane, 2,3-dihexyl-2,3-diphenylbutane, 2-methyl-3-ethyl-2,3-diphenylbutane, 2-methyl-2,3-diphenylbutane, 2,3-diphenylbutane, 2,3-dimethyl-2,3-di-(p-methoxyphenyl)-butane, 2,3-dimethyl-2,3-di-(p-methylphenyl)-butane, 2,3-dimethyl-2-methylphenyl-3-(p 2'3'-dimethyl-3'-methylphenyl-butyl)-phenyl-butane, 3,4-dimethyl-3,4-diphenylhexane, 3,4-diethyl-3,4-diphenylhexane, 3,4-dipropyl-3,4-diphenylhexane, 4,5-dipropyl-4,5-diphenyloctane, 2,3-diisobutyl-2,3-diphenylbutane, 3,4-diisobutyl-3,4-5-diphenylhexane, 2,3-dimethyl-2,3-di-p(t-butyl)-phenyl -Selected from the group consisting of butane, 5,6-dimethyl-5,6-diphenyldecane, 6,7-dimethyl-6,7-diphenyldodecane, 7,8-dimethyl-7,8-di(methoxyphenyl)-tetradecane, 2,3-diethyl-2,3-diphenylbutane, 2,3-dimethyl-2,3-di(p-chlorophenyl)butane, 2,3-dimethyl-2,3-di(p-iodophenyl)butane, and 2,3-dimethyl-2,3-di(p-nitrophenyl)butane.

[0200] In another embodiment, the initiator (E) is selected from the group consisting of 2,3-dimethyl-2,3-diphenylbutane and 3,4-dimethyl-3,4-diphenylhexane.

[0201] Final extrusion polyolefin composition by bis-breaking process The extruded bis-breaked recycled polyethylene-rich polyolefin exiting the extruder has a higher MFR and lower molecular weight than the recycled polyolefin. The extruded bis-breaked recycled polyethylene-rich polyolefin can have an MFR of at least 4 g / 10 min. The increase in MFR of the extruded bis-breaked recycled polyethylene-rich polyolefin can be at least 3 times (i.e., 3 times or 200%) higher than that of the recycled polyolefin. In other embodiments, the extruded bis-breaked recycled polyethylene-rich polyolefin can have an MFR at least 4 times (300%) higher, at least 4.5 times (350%) higher, or at least 5 times (400%) higher than that of the starting recycled polyolefin.

[0202] If the starting MFR of the recycled polyethylene-rich polyolefin is low, for example, less than 10 g / 10 min, the increase in MFR of the extruded bis-breaking recycled polyethylene-rich polyolefin may be even more significant. Therefore, in embodiments of the present invention, the increase in MFR of the extruded bis-breaking recycled polyethylene-rich polyolefin may be 10 times (900%) or more, 12 times (1100%) or more, 13 times (1200%) or more, 14 times (1300%) or more, 15 times (1400%) or more, or 20 times (1900%) or more. The MFR value of the extruded bis-breaking recycled polyethylene-rich polyolefin may be at least 8 g / 10 min, at least 10 g / 10 min, at least 20 g / 10 min, at least 25 g / 10 min, or at least 50 g / 10 min, regardless of the starting recycled polyolefin. The MFR value of the extruded bis-breaking recycled polyethylene-rich polyolefin may be 100 g / 10 min or more.

[0203] Extruded bis-breaked recycled polyethylene-rich polyolefin material does not exhibit significant crosslinking. The degree of crosslinking of extruded bis-breaked recycled polyethylene-rich polyolefin may be less than 0.5% by weight (determined as XHU as described in the examples), less than 0.4% by weight, or less than 0.3% by weight. In some embodiments, crosslinking may be 0.1% by weight or less, or 0.05% by weight or less.

[0204] The density of extruded bis-breaked recycled polyethylene-rich polyolefins (also known as bis-breaked polymers) remains essentially unchanged. Extruded bis-breaked recycled polyethylene-rich polyolefins may be LDPE with a density of 910–1000 kg / m³ or 915–985 kg / m³, MDPE with a density of 926–940 kg / m³, or HDPE with a density of 855–980 kg / m³.

[0205] It should also be noted that the Mw / Mn value of the extruded, bis-breaked recycled polyethylene-rich polyolefin appears to remain unchanged. Therefore, the Mw / Mn can range from 1.5 to 4.0 after extrusion. The pre-extrusion values ​​listed above also apply to the post-extrusion recycled polyolefin.

[0206] The melting point of bis-breaking recycled polyolefins (measured by DSC according to ISO 11357-1) may be less than 100°C, less than 90°C, or less than 85°C. In one embodiment of the present invention, the melting point of ethylene copolymers such as LLDPE is 120°C or less.

[0207] Because the extruded bis-breaked recycled polyethylene-rich polyolefin of the present invention originates from the bis-breaking process rather than directly from the polymerization process, it is likely to contain residues derived from the initiator. For example, if the initiator is one of the above formulas (III), radicals are generated via the splitting of CC bonds, which eliminates the radical groups R1R2R3C· and R4R5R6C·. Since these radicals acquire protons, the resulting compounds may be detected as impurities in the final polymer. Detection methods include NMR. Detection of these compounds confirms that the extruded bis-breaked recycled polymer is derived from bis-breaking, as opposed to direct synthesis.

[0208] The radicals R1R2R3C· or R4R5R6C· may be bound to the polymer chain.

[0209] The extruded, bis-breaked recycled polyethylene-rich polymer may have further additives added as needed, although this is usually not required. However, various amounts of additives, such as pigments, nucleating agents, antistatic agents, fillers, antioxidants, etc., may be present.

[0210] Next, the bis-breaking recycled polyethylene-rich polyolefin is melt-blended to form an extruded bis-breaking polyolefin composition comprising (A) about 60 to about 96% by weight of the extruded bis-breaking recycled polyethylene-rich polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, C) optionally about 2 to about 20% by weight of at least one tackifier, and D) optionally at least one additional polymer, wherein the polyolefin composition has a random alpha-olefin copolymer to tackifier weight ratio of about 0.2 to about 5.0, the polyolefin composition has an increase in melt flow rate of about 5 to about 1500% compared to an unextruded non-bis-breaking recycled polyolefin, and the extruded bis-breaking polyolefin composition has an increase in MFR of about 5 to about 400% compared to the same extruded bis-breaking polyolefin composition that does not contain the melt-blended random alpha-olefin copolymer, optionally tackifier resin and additional polymer. This melt blending step, as well as the random alpha-olefin copolymer and tackifier, have been discussed previously in this disclosure.In at least one embodiment of the present invention, the polyolefin composition comprises a recycled polyethylene-rich polyolefin (A) subjected to a scissor-breaking process resulting in reduced notched impact strength, at least one random alpha-olefin copolymer (B), optionally at least one tackifier (C), and optionally at least one additional polymer (D), wherein the percentage of B+D is about 10 to about 30% by weight or about 10 to about 20% by weight based on the weight of the total polyolefin composition, and the weight ratio of B to D is about 0.3 to about 3.0 or about 0.2 to about 2.0, wherein the extruded scissor-breaked polyolefin composition has an increase of about 5 to 100% in MFR and an increase of about 5 to about 200% in notched impact strength compared to the same extruded scissor-breaked polyolefin composition without the random alpha-olefin copolymer, optionally tackifier resin, and additional polymer, and the extruded scissor-breaked polyolefin composition maintains acceptable mechanical properties.

[0211] In at least one embodiment of the present invention, the polyolefin composition comprises a recycled polyethylene-rich polyolefin (A) subjected to a bis-breaking process resulting in reduced notched impact strength, at least one random alpha-olefin copolymer (B) having a glass transition temperature of -10°C or lower (ASTM D 3418-15) and a nominal molecular weight of 25,000 g / mol or lower (ISO 16014), and optionally a polyolefin having a glass transition temperature of 45°C or higher (ASTM D 3418-15). The extruded stippled polyolefin composition comprises at least one tackifier (C) having 3418-15) and optionally at least one additional polymer (D), wherein the percentage of B+D is about 10 to about 30% by weight or about 10 to about 20% by weight based on the weight of the total polyolefin composition, and the weight ratio of B to D is about 0.3 to about 3.0 or about 0.2 to about 2.0, and the extruded stippled polyolefin composition has an increase of about 5 to 100% in MFR and an increase of about 5 to about 200% in notched impact strength compared to the same extruded stippled polyolefin composition without random alpha-olefin copolymer, optional tackifier resin, and additional polymer, and the extruded stippled polyolefin composition maintains acceptable mechanical properties.

[0212] In at least one embodiment of the present invention, a polyolefin composition is provided comprising an extruded polyethylene-rich recycled polyolefin (A) subjected to a screw-breaking process that results in reduced notched impact strength, at least one random alpha-olefin copolymer (B), optionally at least one tackifier (C), and optionally at least one additional polymer (D), wherein the additional polymer is not limited to linear low-density polyethylene, medium-density polyethylene, ethylene methyl acrylate copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, or ethylene-octen copolymer, and the extruded screw-breaking process is provided. The broken polyolefin composition is prepared such that the percentage of B+D is about 10 to about 30% by weight, more preferably about 10 to 20% by weight, based on the weight of the total polyolefin composition, and the weight ratio of B to D is 0.3 to 3.0, more preferably 0.2 to 2.0. The extruded bis-broken polyolefin composition has an increase of about 5 to about 100% in MFR and an increase of about 5 to about 200% in notched impact strength compared to the same extruded bis-broken polyolefin composition that does not contain random alpha-olefin copolymers, optional tackifier resins, and additional polymers, and the polyolefin composition maintains acceptable mechanical properties.

[0213] In at least one embodiment of the present invention, a polyolefin composition is provided comprising: polyethylene-rich recycled polyolefin (A) subjected to a scissor-breaking process resulting in reduced notched impact strength; at least one random alpha-olefin copolymer (B) having a glass transition temperature of -10°C or lower (ASTM D 3418-15) and a nominal molecular weight of 25,000 g / mol or lower (ISO 16014); optionally, at least one tackifier (C), (C) having a glass transition temperature of 45°C or higher (ASTM D 3418-15); and optionally, at least one additional polymer (D), the additional polymer being, but not limited to, linear low-density polyethylene, medium-density polyethylene, ethylene methyl acrylate copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, or ethylene-octene copolymer, wherein the extruded scissor-breaking polyolefin composition has a percentage of B+D of about 10 to about 30 based on the weight of the total polyolefin composition. The extruded styrofoam-breaking polyolefin composition is prepared such that the amount of polymer is approximately 10-20% by weight, and the weight ratio of B to D is 0.3-3.0, more preferably 0.2-2.0, and has an increased MFR of approximately 5-100% and an increased notched impact strength of approximately 5-200% compared to the same extruded styrofoam-breaking polyolefin composition that does not contain random alpha-olefin copolymers, optionally tackifier resins, and additional polymers, while the extruded styrofoam-breaking polyolefin composition maintains acceptable mechanical properties.

[0214] In at least one aspect of this embodiment, the extruded bis-breaking polyolefin composition also exhibits an increase of about 5–100% in MFR and an increase of about 5–100% in yield point elongation compared to the same extruded bis-breaking polyolefin composition that does not contain random alpha-olefin copolymers, optional tackifier resins, and additional polymers, while maintaining acceptable mechanical properties.

[0215] In another aspect of this embodiment, the additional polymer (D) is an unused polymer having fractional melt MFR (<1 measured at 190°C and 2.16 kg according to ISO 1133), and in yet another aspect of this embodiment, the additional polymer is a recycled polyolefin having 100-1000% higher notched impact strength compared to recycled polyethylene-rich polyolefin (A) after bis-breaking.

[0216] In at least one embodiment, the polyolefin composition is prepared in a second process step after bis-breaking by melt blending, as described above in this disclosure. After the bis-breaking step and before the melt blending step, the bis-breaked polyethylene-rich recycled polyolefin can be stored in the form of pellets, flakes, or powder, but not limited to those known to the art, under conditions known to those skilled in the art. In at least one embodiment, the bis-breaked polyethylene-rich polyolefin can be stabilized with additives known to those skilled in the art and stored in molten form.

[0217] In at least one other embodiment, the bis-breaked polyethylene-rich recycled polyolefin is supplied directly to the melt-blending process without intermediate storage. The melt-blending process (following inline with the bis-breaking process) to obtain the extruded bis-breaked polyolefin composition can only be carried out when the bis-breaked polyethylene-rich recycled polyolefin has been sufficiently cooled, preferably below 250°C, more preferably below 220°C, to enable proper supply and melt-blending. This melt-blending process is discussed earlier in this disclosure.

[0218] In another specific aspect of this embodiment, the input level of random alpha-olefin copolymers and / or tackifiers and / or additional polymers in an extruded bis-breaking polyolefin composition can be metered by measuring the melt viscosity of the bis-breaking polyethylene-rich recycled polyolefin using an in-line rheometer and adjusting the input level based on this measured melt viscosity to achieve a target melt viscosity. Such in-line rheometers are available from companies such as Haake, Leistritz, and Brabender.

[0219] Purpose In another embodiment of the present invention, articles comprising a polyolefin composition are provided. Articles include, but are not limited to, films (e.g., single-layer or multi-layer films for packaging, uniaxial or biaxially oriented films, cast films, shrink films, overlap films, lamination films, laminated films, blow films for plastic bags, agricultural films, protective films for coating parts or mobile phone screens, protective packaging films, films for vertical molding, filling and sealing packaging, films for horizontal molding, filling and sealing packaging, building films for underslab moisture barriers, sheets, extruded parts (e.g., single, co- and multi-extruded profiles, tubes, fibers and pipes, overcoated wires), injection molded parts (e.g., battery cases), blow molded parts (e.g., rigid packaging, bottles and household automobiles, containers for food or personal care), thermoformed articles (e.g., deep-drawn containers or cups for household care, food or personal care), rotationally molded articles (e.g., water tanks), woven and nonwoven fabrics, and foamed articles (e.g., sealing gaskets). Additional articles include carpets. Examples of applications include sheets, flooring materials, roofing materials, composite materials (e.g., exterior decking), synthetic paper, artificial turf, fibers, thermoplastic elastomers (e.g., TPO sheets or (over)molded articles), automotive parts (e.g., dashboards and window seals), computer parts, healthcare parts, building materials, home appliances, electronic components, electrical components, toys, and footwear parts. The films of this disclosure include any suitable film structures and film applications. Specific end-use films include, for example, blow films, cast films, stretch films, stretch / cast films, stretch cling films, stretch hand-wrap films, mechanical stretch wraps, shrink films, shrink wrap films, greenhouse films, laminates, and laminate films. Exemplary films are prepared by any suitable technique, such as, for example, blow, extrude, and / or cast stretch and / or shrink films. Multilayer films (or multiple-layer films) may be formed by any suitable method. The total thickness of multilayer films may vary depending on the desired application.Sheets prepared from the compositions of this disclosure may be used to form containers. Such containers may be formed by thermoforming, solid-state pressure forming, stamping, and other forming techniques. The sheets may also be unfolded in a fan shape to cover a floor, wall, or other surface.

[0220] The compositions of the present invention may be formed into articles by one of several conventional processes and apparatus known to those skilled in the art. Exemplary processes include, but are not limited to, casting, extrusion, extrusion coating, co-extrusion, extrusion foaming, compression molding, calendering, injection molding, thin-wall injection molding, low-pressure molding, direct injection expansion foaming, compression molding, transfer molding, blow molding, rotational molding, or combinations thereof such as thermoforming or biaxial orientation following extrusion. Combinations of processes may be carried out in line or as processes consisting of separate production steps that allow for intermediate storage of semi-finished products (e.g., secondary orientation of extruded films). Articles may also be prepared by in-situ melting processes such as thermal setting processes or by cold forming processes also known as solid-phase formation. In addition, articles may be prepared by additive manufacturing processes, including, but not limited to, stereolithography (SLA), fuse deposit melting (FDM), selective laser sintering (SLS), multi-jet fusion (MJF), polyjet, vacuum casting, or a combination thereof.

[0221] It is implied in embodiments of the present invention that the compositions described herein may also contain unused polyolefin polymers, and those skilled in the art can modify compositions containing up to 96% by weight of unused polyolefin polymers, based on the weight of the composition, using this specification and the claims appended thereto. The unused polymers may be identical (except for expiration date) or different from recycled polyolefins or the majority of recycled polyolefin polymers. [Examples]

[0222] These and other aspects of the present invention can be better understood by referring to the following examples, which are merely illustrative of preferred embodiments of the present invention and should not be construed as limiting the invention.

[0223] Table 1 shows the materials used in Examples 1 to 19.

[0224] [Table 1] * PCR PE contains small percentages of polypropylene (<0.5%) and carbon black (<1.3%), but also contains trace amounts of other polymers (<0.03% of polyvinyl chloride, polyethylene terephthalate, polycarbonate, polystyrene, acrylonitrile-butadiene-styrene, polyamide, and polyurethane).

[0225] The meaning of the symbols used in these examples, the units used to represent the variables mentioned, and the methods for measuring these variables are explained below.

[0226] The methods for testing the data in Examples 1 to 23 are provided in Table 2 below.

[0227] [Table 2] * Universal test specimens were prepared by injection molding using an Engel Victory VC 300 / 80 Tech pro injection molding machine (clamping force 800kN and screw diameter 35mm) with a screw temperature profile of 200-230°C and a set mold cavity temperature of 25°C.

[0228] Examples 1-8 Polyethylene-rich PCR modified with MB containing a tackifier or random alpha-olefin copolymer Based on the weight of the polyolefin composition, the polyolefin composition comprises 89.9-99.9% by weight of post-consumer polyethylene (PCR PE) with an MFR of 0.8 (190°C, 2.16 kg), 0-2% by weight of fully hydrogenated hydrocarbon tackifier resin (Plastolyn® R1140), 0-5% by weight of amorphous poly-alpha-olefin (Aerafin® 17), and 0.1% by weight of antioxidant / stabilizer (Irganox® 1010 and Irgafos® 168), PCR PE, a 50% masterbatch of Plastolyn® R1140 in unused low-density polyethylene with an MFR of 22 (190°C, 2.16 kg), and unused low-density polyethylene with an MFR of 22 (190°C, 2.16 kg). The mixture was prepared by manually dry-blending a 50% masterbatch of Aerafin® 17 amorphous poly-alpha-olefin in polyethylene (LDPE) with powdered Irganox® 1010 and Irgafos® 168, and then compounding it in a Leistritz twin-screw extruder at a screw temperature profile of 145–160°C and a screw speed of 170 rpm. The compositions and properties of the examples are shown in Tables 3 and 4. The masterbatch was manually dry-blended and then compounded in a Leistritz twin-screw extruder at a screw temperature profile of 85–135°C and a screw speed of 170 rpm.

[0229] [Table 3]

[0230] The results in Table 3 demonstrate the improved properties of the present invention, surpassing the denaturation of PCR PE by either hydrogenated hydrocarbon resin alone or amorphous poly(alpha-)olefin alone in Comparative Examples 3-6. Single addition of amorphous poly(alpha-)olefin at levels required to have a significant increase in MFR resulted in a decrease in yield point tensile strength (Comparative Example 4), while lower levels of addition did not show the desired increase in MFR (Comparative Example 3). Single addition of hydrogenated hydrocarbon resin at levels required to have a significant increase in MFR resulted in a decrease in Charpy impact strength (Comparative Example 6), while lower levels of addition did not show the desired increase in MFR (Comparative Example 5). The results for MFR, yield point tensile strength, and Charpy impact strength in Invention Example 2 show surprisingly unexpected improvements compared to the comparative examples when both hydrogenated hydrocarbon tackifier resin and amorphous poly(alpha-)olefin are added.

[0231] [Table 4] * The results from Calculation Example 8 are a weighted average of the results from Examples 4 and 5, assuming linearity in the influence of the total input percentage of hydrogenated hydrocarbon resin and amorphous poly(alpha-)olefin on the variables. This linearity was verified for MFR, tensile modulus and yield strength and is accurate for input levels of 0-10%, as shown in Examples 13-16 and 18-20. 2 It is proven to yield a linear fit of >0.97.

[0232] The results in Table 4 demonstrate the improved properties of the present invention (Example 7) which surpass the calculated properties of PCR PE modification with hydrogenated hydrocarbon resin and amorphous poly(alpha-)olefin (Calculation Example 8). The increase in MFR is higher than the MFR calculated based on the increase in weight-average MFR due to the addition of hydrogenated hydrocarbon resin or amorphous poly(alpha-)olefin alone (Calculation Example 8). Unexpectedly, the yield strength also exceeds the expected yield strength in Calculation Example 8.

[0233] Examples 9-11 Modification of polypropylene-rich PCR using MB containing tackifier resin or random alpha-olefin copolymer Based on the total weight of the polyolefin composition, polyolefin compositions comprising 80-100% by weight of post-consumer polypropylene (PCR PP), 0-10% by weight of amorphous poly-alpha-olefin (Aerafin® 17), and 0-2% by weight of fully hydrogenated hydrocarbon tackifier resin (Plastolyn® R1140) were prepared by manually dry-blending PCR PP with a 50% by weight masterbatch of Aerafin® 17 in unused polypropylene having an MFR of 25 (230°C, 2.16 kg) and a 50% by weight masterbatch of Plastolyn® R1140 in unused polypropylene having an MFR of 25 g / 10 min, followed by compounding in a Collin ZK25P twin-screw extruder at a screw temperature profile of 150-210°C and a screw speed of 250 rpm. The compositions and properties of the examples are shown in Table 5. The masterbatch was manually dry-blended and then compounded in a Leistritz twin-screw extruder with a screw temperature profile of 120-180°C and a screw speed of 130 rpm.

[0234] [Table 5]

[0235] The results in Table 5 demonstrate the improved properties of the present invention, surpassing the denaturation of PCR PP by amorphous poly(alpha-)olefin alone in Example 11. The increase in MFR is higher than that of the case where amorphous poly(alpha-)olefin alone was added (Example 10).

[0236] Comparative Examples 12-16: Random alpha-olefin copolymers in PCR PE Comparative polyolefin compositions containing 80-95% by weight of post-consumer polyethylene (PCR PE) and 2.5-10% by weight of amorphous poly-alpha-olefin (Aerafin® 17) were prepared by compounding in a Collin ZK25P twin-screw extruder at a screw temperature profile of 150-210°C and a screw speed of 200 rpm, based on the total weight of the polyolefin composition. After manually dry-blending a 50% by weight masterbatch of Aerafin® 17 and PCR PE in unused low-density polyethylene with an MFR of 7.5 g / 10 min (190°C, 2.16 kg), the masterbatch and post-consumer polyethylene were manually dry-blended and then compounded in a Leistritz twin-screw extruder at a screw temperature profile of 85-135°C and a screw speed of 170 rpm. Reference Example 12 was similarly prepared without the addition of the Aerafin® 17 masterbatch.

[0237] [Table 6]

[0238] The results in Table 6a support the assumption of linearity of the effect on the variable relating to the total percentage of amorphous poly(alpha-)olefins added (as made in Example 8).

[0239] Comparative Examples 17-20: Tackifying Resins in PCR PP Comparative polyolefin compositions, based on the total weight of the polyolefin composition, comprising 80–95% by weight of polypropylene homopolymer (Moplen HP400H) and 5–20% by weight of fully hydrogenated hydrocarbon tackifier resin (Plastolyn® R1140), were dry-blended using a 20% masterbatch of Plastolyn® R1140 in Moplen HP400H prepared by compounding in a Coperion ZSK 18 co-rotating 18mm twin-screw extruder with a screw temperature profile of 80–190°C and a screw speed of 300 rpm. Universal test specimens were prepared from the dry blends by injection molding using an Engel Victory VC 300 / 80 Tech pro injection molding machine (800kN clamping force and 35mm screw diameter) with a screw temperature profile of 200–220°C and a set mold cavity temperature of 15°C. Reference Example 17 was similarly prepared without the addition of a Plastolyn® R1140 masterbatch.

[0240] [Table 7]

[0241] The results in Table 6b support the assumption of linearity of the effect on the variable relating to the total percentage of hydrogenated hydrocarbon resins used (as made in Example 8).

[0242] Table 7 shows the materials used in Examples 21-23.

[0243] [Table 8] * PCR PE contains small percentages of polypropylene (<0.5%) and carbon black (<1.3%), but also contains trace amounts of other polymers (<0.03% of polyvinyl chloride, polyethylene terephthalate, polycarbonate, polystyrene, acrylonitrile-butadiene-styrene, polyamide, and polyurethane).

[0244] Comparative Example 21: Extrusion of PCR PE Compounds containing 100% post-consumer polyethylene (PCR PE, 0.8 MFR) were prepared by compounding them in a Collin ZK 25E LD 42 twin-screw extruder with a screw temperature profile of 250-350°C and a screw speed of 150 rpm.

[0245] Comparative Example 22: Viscosity Breaking of PCR PE Compounds containing 99.9% post-consumer polyethylene (PCR PE, 0.8 MFR) and 0.1% 2,3-dimethyl-2,3-diphenylbutane (radical initiator) were prepared by manually dry-blending the PCR PE with the radical initiator, followed by compounding in a Collin ZK 25E LD 42 twin-screw extruder with a screw temperature profile of 250–350°C and a screw speed of 150 rpm.

[0246] Invention Example 23: Modification of bis-breaking rPE with random alpha-olefin copolymers Compounds containing 79.7% Comparative Example 22, 10% amorphous poly-alpha-olefin (Aerafin® 17), and 0.3% antioxidants / stabilizers (Irganox® 1010 and Irgafos® 168) were prepared by manually dry-blending Comparative Example 22, which had a 50% masterbatch of Aerafin® 17 in unused low-density polyethylene with an MFR of 7.5 (190°C, 2.16 kg), and a 75% masterbatch of Irganox® 1010 and Irgafos® 168 in calcium stearate (Irganox® 1010 to Irgafos® 168 in a 1:2 ratio), followed by compounding in a Collin ZK 25E LD 42 twin-screw extruder with a screw temperature profile of 145–170°C and a screw speed of 20 rpm. The Aerafin® 17 masterbatch was manually dry-blended and then compounded in a Leistritz twin-screw extruder with a screw temperature profile of 120–180°C and a screw speed of 130 rpm.

[0247] [Table 9]

[0248] The results in Table 8 demonstrate the improved properties of the present invention (Example 23) compared to the denaturation of PCR PE by high-temperature extrusion (Comparative Example 21) or high-temperature extrusion (vis-breaking) in the presence of a radical initiator (Comparative Example 22). Denaturation with amorphous poly-alpha-olefin after high-temperature extrusion (vis-breaking) in the presence of a radical initiator results in a 62.9% higher MFR than high-temperature extrusion in the presence of a radical initiator alone, and a 430% higher MFR compared to high-temperature extrusion in the absence of a radical initiator. Compared to the original undenatured PCR PE, Example 23 shows a 1160% higher MFR.

[0249] Table 9 shows the materials used in the following Examples 24 to 51.

[0250] [Table 10] * PCR PE2 contains small percentages of polypropylene (<0.5%), CaCO3 (<1.5%), and inorganic pigments (<0.5%), but also contains trace amounts of other polymers (<0.03% of polyvinyl chloride, polyethylene terephthalate, polycarbonate, polystyrene, acrylonitrile-butadiene-styrene, polyamide, and polyurethane).

[0251] The data testing methods used in Examples 24-51 are provided in Table 10 below.

[0252] [Table 11] *Tensile test specimens were prepared by injection molding using a Toyo injection molding machine (90-ton clamping force and 32 mm screw diameter) with a screw temperature profile of 170 to 195°C and a set mold cavity temperature of 20°C.

[0253] Example 24 PCR PE Composition Prepared Using Masterbatch Three masterbatches (MB) were compounded on a Werner & Pfleiderer twin-screw extruder with a diameter of 40 mm and an L / D ratio of 40 / 1, at the compositions, screw temperature profiles and screw speeds listed in Table 11. Two raw material feeders for the random alpha-olefin copolymer or tackifier resin and the carrier polymer were utilized at the main hopper during the masterbatch process.

[0254] [Table 12]

[0255] A polyolefin composition comprising 90 wt% post-consumer polyethylene (PCR PE2), 5 wt% fully hydrogenated hydrocarbon tackifier resin (Eastotac™ H-142W), and 5 wt% Dowlex™ 2045G LLDPE carrier, based on the weight of the polyolefin composition, was obtained by manual dry blending with the aforementioned 50% masterbatch of Eastotac™ H-142W tackifier resin in virgin Dowlex™ 2045G linear low density polyethylene carrier (MFR of 1.0 at 190°C, 2.16 kg). The blend was injection molded using a 90-ton Toyo injection molding machine with a barrel temperature profile of 170 to 195°C and a mold cavity temperature of 20°C.

[0256] Examples 25 to 34 PCR PE Compositions Prepared Using Masterbatch The polyolefin compositions of Examples 25 to 34 were prepared in the same manner as Example 24, and the compositions and properties are as shown in Tables 12 and 13. Reference Example 30 was also prepared in the same manner as Example 24, except that no random alpha-olefin copolymer or tackifier resin was added.

[0257] All examples show an increase in MFR measured at 190°C and 2.16 kg. Analysis of the data and compositions showed that the LLDPE carrier, the random alpha-olefin copolymer, and the tackifier resin all contribute to the increase in MFR, however, surprisingly, the increase was not linear with the weight percent of each component.

[0258] Inventive Example 31, which contains 5 wt% each of Aerafin 17 and Eastotac H-142W, shows a surprising 289% increase in elongation compared to the original PCR of Reference Example 30, while Comparative Example 28 with 5% Aerafin 17 provides a 104% increase in elongation, and Comparative Example 24 with 5% resin Eastotac H-142W provides only a 49% increase in elongation.

[0259] Inventive Example 34, in which 5% Plastolyn R1140 resin was added to the composition of Comparative Example 29, shows a surprising 526% increase in elongation compared to the original unmodified PCR of Reference Example 30, while Example 29 with 10% Aerafin 17 provides a 299% increase in elongation, and Comparative Example 27 with 10% resin Plastolyn R1140 provides only a 93% increase in elongation.

[0260] Inventive Example 33, in which 10% Eastotac H-142W resin was added to the composition of Example 28, showed a remarkable 589% increase in elongation compared to the original PCR in Reference Example 30, whereas Example 28 yielded a 104% increase in elongation with 5% Aerafin 17, and Example 25 yielded only a 130% increase in elongation with 10% Eastotac H-142W resin. This increase in MFR and elongation resulted in a more favorable balance of MFR and physical properties than could be obtained using either the tackifier resin alone or the random alpha-olefin copolymer alone.

[0261] Comparative Examples 24-27 demonstrate that adding only hydrogenated hydrocarbon resin to an LLDPE carrier resin reduces the notched Izod impact strength by as much as 84%. These compositions contained as much as 20% LLDPE.

[0262] The notched izod impact values ​​at room temperature could not be measured on the dogbone of the carrier LLDPE due to its extremely high flexibility. Surprisingly, Examples 28-29 and Inventive Examples 31-34, which contained a high LLDPE level of 45% in the polyolefin composition, were found to exhibit improved notched izod compared to the original PCR PE in Reference Example 30. The notched izod of the examples containing only random alpha-olefin polymers (Comparative Examples 28 and 29) were 45% and 142% higher than the original PCR (Reference Example 30), while Inventive Examples 31-34 had notched izod values ​​ranging from 38% to 159% higher than the original PCR.

[0263] Other polymers can also be incorporated into the masterbatch composition to improve the impact performance or other physical properties of the final composition.

[0264] [Table 13]

[0265] [Table 14]

[0266] Example 35 Modification of polypropylene-rich post-consumer polyolefins via masterbatch Preparation of PP masterbatches used in Examples 35-44 The masterbatch (MB) was compounded in a 40 mm diameter, 40 / 1 L / D Werner & Pfleiderer twin-screw extruder with the screw temperature profiles and screw speeds listed in Table 14. Two raw material feeders for random alpha-olefin copolymers or tackifier resins and carrier polymers were used in the main hopper during the masterbatch process.

[0267] [Table 15]

[0268] A polyolefin composition comprising 80 wt% polypropylene-rich post-consumer polyolefin (PCR PP), 10 wt% fully hydrogenated hydrocarbon resin (Eastotac® H-142W), and 10 wt% Pinnacle® 1112 carrier (MFR 12 g / 10 min, 230°C, 2.16 kg) was obtained by manually dry blending the aforementioned 50% masterbatch of Eastotac® H-142W fully hydrogenated hydrocarbon resin in unused Pinnacle® 1112 polypropylene carrier having an MFR of 12.0 (230°C, 2.16 kg). The blend was injection molded in a 90-ton Toyo injection molding machine with a barrel temperature profile of 170–195°C and a mold cavity temperature of 20°C.

[0269] Examples 36-44 Modification of polypropylene-rich post-consumer polyolefins via masterbatch The polypropylene-rich polyolefin compositions of Examples 36 to 44 were prepared in the same manner as Example 35, and the compositions and properties are as shown in Tables 15 and 16. Reference Example 39 PCR PP was prepared without adding a random alpha-olefin copolymer or a tackifier resin.

[0270] [Table 16]

[0271] [Table 17]

[0272] Inventive Example 43 shows that the addition of 5% Plastolyn R1140 resin to the composition of Comparative Example 38 results in an MFR that is 31% higher than that of unmodified PP PCR (Reference Example 39), which is twice the percent improvement obtained from the addition of 5% Plastolyn R1140 alone in Comparative Example 36. This inventive example also exhibits unexpected increases in flexural strength (39%) and flexural modulus (84%) over the values of unmodified PP PCR, and these values were also greater than those of Comparative Example 38 containing only 5% Aerafin 17 APO.

[0273] Inventive Example 44 combines 10% Plastolyn R1140 resin with 5% Aerafin 17 APO to produce even greater increases over the values of unmodified PP PCR in MFR (58%), flexural strength (45%), and flexural modulus (104%). Surprisingly, the Young's modulus also increased (15%) beyond the values of unmodified PP PCR (Reference Example 39) and Comparative Example 38. The surprisingly improved properties of Inventive Examples 43 and 44 provided a more advantageous balance of MFR and physical properties than that obtained using either the tackifier resin alone or the random alpha-olefin copolymer alone.

[0274] Invention Example 42, containing 5% Eastotac H-142W resin and 10% Aerafin 17 APO, exhibited a higher MFR than Comparative Example 41, which contained only 10% Aerafin 17 APO. In addition, this invention example surprisingly exhibited a 152% greater elongation at break than unmodified PCR PP while maintaining other physical properties. The elongation of this invention example was also greater than that of Comparative Examples 41 and 35, which contained equal amounts of random alpha-olefin copolymer alone or tackifier resin alone, respectively.

[0275] Examples 45-51 PCR PE compositions prepared by direct addition Dry blend samples without a masterbatch were fully compounded in an 18 mm diameter, 40 / 1 L / D Leistritz twin-screw extruder at the screw temperature profiles and screw speeds listed in Table 17. A single raw material feeder for the dry blend mixture of random alpha-olefin copolymers and / or tackifier resins with PCR PE2 was used in the main hopper throughout the entire compounding process.

[0276] The test specimens were prepared by injection molding in a 90-ton Toyo injection molding machine with a barrel temperature profile of 170–195°C, a screw diameter of 32 mm, and a mold cavity temperature of 20°C.

[0277] [Table 18]

[0278] Examples 45-51 increased the MFR of the compound by 49%-114% compared to that of Example 45, and increased the break point elongation of the compound by 4%-70% compared to the elongation of the unmodified Reference Example 45. Surprisingly, Inventive Examples 47, 49, and 51, which included both the tackifier resin and amorphous poly-alpha-olefin, significantly increased the break point elongation beyond the elongation obtained when amorphous poly-alpha-olefin alone was added to unmodified PCR PE2. For example, Example 47 showed a 70% greater elongation than unmodified PCR PE compared to the 19% greater elongation obtained in Comparative Example 46, and Inventive Example 49 had a 41% greater elongation than unmodified PCR PE compared to the 4% greater elongation of Comparative Example 48. The unexpected interaction between the tackifier resin, random alpha-olefin copolymer, and PCR improves the rheological properties (fluidity) of PCR and provides the ability to balance the physical properties of the polyolefin composition with the needs of the target application.

[0279] Surprisingly, the test standard deviation for denatured PCR samples was found to be significantly lower than that for undenatured PCR samples. This significant reduction in test variability indicates that denatured PCR polyolefin compositions have more consistent composition and quality than undenatured PCR.

[0280] [Table 19]

[0281] The additional materials used in the following examples are listed in Table 19 below. The test methods used are shown in Table 2.

[0282] [Table 20]

[0283] Examples 52-56 Modification of rHDPE with MB containing either random alpha-olefin and ethylene-1-octene or ethylene-1-hexene MDPE polyolefin polymer Two masterbatches were produced using a Leistritz twin-screw extruder with a screw temperature profile of 135–165°C and a screw speed of 150 rpm, after manual dry blending of the components.

[0284] Masterbatch MB1 was prepared using 50 wt% Elite® 5940ST, a medium-density fractionally melted C8 reinforced polyethylene resin (MDPE) from DOW, and 50 wt% Aerafin® 180, a propylene-ethylene amorphous random copolymer.

[0285] Masterbatch MB2 was prepared using 50 wt% Enable® 4009 MC blown medium-density fractionated molten ethylene 1-hexene copolymer from Exxon Mobile, and 50 wt% Aerafin® 180 propylene-ethylene amorphous random copolymer.

[0286] [Table 21]

[0287] Using both MB1 and MB2, recycled polyethylene-rich HDPE streams (PCR PE) with reduced impact strength were denatured by exposure to a viscosity breaking (bisbreak) process that induces chain breaks in the presence of radical initiators and exposure to high temperatures, e.g., above 320°C. This process reduced the Charpy notch impact strength of the bisbreaked recycled HDPE (Reference Example 52) to 35.8 kJ / m². 2 From 4.1 kJ / m 2 Reduced to (ISO179-1).

[0288] Using a Collin ZK25P twin-screw extruder with a screw temperature profile of 145–170°C and a screw speed of 200 rpm, 10% by weight or 20% by weight of MB1 or MB2 was blended into the described screw-breaking recycled HDPE. Injection-molded test rods were prepared using the resulting polyolefin compositions, and their MFR, tensile properties, and notched impact strength were evaluated. Tables 21 and 22 below list the compositions and measured properties.

[0289] [Table 22]

[0290] [Table 23]

[0291] Examples 53-56 showed a 30%-90% increase in notched Charpy impact strength compared to the unmodified reference, and simultaneously, examples 53-56 showed a 25%-50% increase in MFR, both of which were caused by the combination of fractionally melted MDPE and low-viscosity amorphous polyolefin.

[0292] Examples 57-63 Modification of screw-breaking r-HDPE by direct addition of random alpha-olefins and MDPE Eltex® HD3930UA, a linear medium-density polyethylene grade from Ineos Olefins & Polymers (Rolle, Switzerland), was used in combination with Aerafin® 180, a propylene-ethylene amorphous random copolymer from Eastman Chemical (Kingsport, TN, USA), to modify recycled HDPE streams whose impact strength was reduced due to exposure to a viscosity breaking (bisbreak) process that induces chain severance in the presence of a radical initiator and to high temperatures, e.g., above 320°C. This process reduced the Charpy notch impact strength of the bisbreaked recycled HDPE to 35.8 kJ / m². 2From 4.1 kJ / m 2 Reduced to (ISO 179-1).

[0293] Using a Collin ZK25P twin-screw extruder with a screw temperature profile of 145–170°C and a screw speed of 200 rpm, 20% by weight, 40% by weight, or 60% by weight of Eltex HD3930UA was blended alone or in combination with 5% by weight of Aerafin 180 into the described screw-breaking recycled HDPE. Aerafin 180 was dry-blended with the screw-breaking recycled HDPE and added to the main hopper, and Eltex HD3930UA was added using a second feed hopper; both were introduced at the inlet of the blender. Injection-molded test rods were prepared using the resulting polyolefin compositions, and the MFR, tensile properties, and notched impact strength were evaluated. Tables 23 and 24 below list the blend compositions and the measured properties.

[0294] [Table 24]

[0295] [Table 25]

[0296] Table 24 shows that the inclusion of additional polymers improved notched impact strength and reduced the MFR of the recycled polyolefin composition by 12% to 24% compared to Comparative Examples 57-59 while maintaining elongation. Invention Examples 61-63 demonstrate unexpectedly greater improvements in impact performance based on the properties of the additional MDPE polymer and random alpha-olefin copolymer, as well as a reduction in MFR reduction due to the addition of lower MFR MDPE (e.g., Invention Example 61 compared to Comparative Example 57). The notched Charpy impact strength of Invention Example 62 is 15% higher compared to Comparative Example 58. In particular, the inventors were surprised to find that Invention Example 61, containing both the additional polymer and the random alpha-olefin copolymer, had the same MFR as the unmodified Reference Example 52 bis-breaking r-HDPE PCR PE (14% higher than Comparative Example 57 with only the additional polymer), a yield elongation 17% higher than Comparative Example 57, and a notched Charpy impact strength 28% higher than Comparative Example 57.

[0297] Examples 64-67: Modification of bis-breaking PCR PE with random alpha-olefin and ethylene-acrylate copolymers via masterbatch. The first masterbatch (MB3) was prepared using 50 wt% EMAC® SP2202, a medium-viscosity ethylene acrylate copolymer, and 50 wt% Aerafin® 180, a propylene-ethylene amorphous random copolymer (Eastman), from Westlake Chemicals (Houston, Texas, USA). This MB was produced in a 26 mm twin-screw extruder manufactured by Coperion at a processing temperature of 80–190°C and 150 screw rpm. Two separate feeders were used to precisely control the feed rates of EMAC® SP2202 and Aerafin® 180, which were supplied through the main hopper. The total yield obtained was 9 kg / hour.

[0298] A second masterbatch (MB4) was prepared using the same process with 50 wt% EMAC® SP2205 from Westlake Chemicals, a medium viscosity ethylene acrylate copolymer, and 50 wt% Aerafin® 180.

[0299] [Table 26]

[0300] Recycled post-consumer HDPE streams (PCR PE) with reduced impact strength were denatured by exposure to a viscosity breaking (visbreak) process in which chain breaks are induced in the presence of radical initiators, and by exposure to high temperatures, e.g., above 320°C, using MB3 and MB4. This process resulted in a notched impact strength of 35.8 kJ / m². 2 From 4.1 kJ / m 2 Reduced to (ISO 179-1).

[0301] Using a Collin ZK25P twin-screw extruder with a screw temperature profile of 145–170°C and a screw speed of 200 rpm, 10% by weight or 20% by weight of MB3 or MB4 was blended into screw-breaking recycled HDPE. Injection-molded test rods were prepared using these compounds, and their MFR, tensile properties, and notched impact strength were evaluated. Table 26 lists the blend compositions. Table 27 lists the measured properties of the prepared polyolefin compositions.

[0302] [Table 27]

[0303] [Table 28]

[0304] As shown in Table 27, the compositions of the present invention containing both ethylene-acrylate copolymer and random alpha-olefin copolymer (Examples 64-67) all surprisingly show a simultaneous increase in MFR and notched impact strength. Example 56 shows a 51% increase in MFR and a remarkable 216% increase in notched impact strength compared to the unmodified styrofoamed r-HDPE (PCR PE) of Reference Example 52. In addition, the examples also show an unexpected 20%-34% increase in yield elongation compared to Reference Example 52.

Claims

1. A process for producing a polyolefin composition, comprising melt-blending (A) about 60 to about 96% by weight of at least one recycled polyolefin, B) about 2 to about 20% by weight of at least one random alpha-olefin copolymer, C) about 2 to about 20% by weight of at least one tackifier, and D) optionally, at least one additional polymer, wherein the polyolefin composition has a weight ratio of about 0.2 to about 5.0 random alpha-olefin copolymer to tackifier, and the polyolefin composition has an increase in melt flow rate of about 5 to about 400% compared to the same polyolefin composition without the random alpha-olefin copolymer, the tackifier, and the optionally additional polymer.

2. The process according to claim 1, wherein the recycled polyolefin (A), the random alpha-olefin copolymer (B), and the tackifier (C) are in the form of pellets, granules, powder, flakes, or a combination thereof, and the pellets, granules, powder, or flakes of the random alpha-olefin copolymer are optionally coated or sprinkled with polyethylene wax, polypropylene wax, talc, or silico to improve processability.

3. The random alpha-olefin copolymer (B) is an amorphous polypropylene homopolymer, an amorphous polypropylene-ethylene copolymer, and one or more C 4 ~C 10 The process according to claim 1, selected from the group consisting of amorphous polypropylene-ethylene copolymers containing alpha-olefin derivative units, or combinations thereof.

4. The process according to claim 1, wherein the tackifier (C) is selected from alicyclic hydrocarbon resins, C5 hydrocarbon resins, C5 / C9 hydrocarbon resins, aromatically modified C5 resins, C9 hydrocarbon resins, pure monomer resins, C5 resins, C9 resins, terpene resins, terpene phenol resins, terpene styrene resins, rosin esters, modified rosin esters, fully or partially hydrogenated rosin liquid resins, fully or partially hydrogenated rosin esters, fully or partially hydrogenated modified rosin resins, fully or partially hydrogenated rosin alcohols, fully or partially hydrogenated C5 resins, fully or partially hydrogenated C5 / C9 resins, fully or partially hydrogenated aromatically modified C5 resins, fully or partially hydrogenated C9 resins, fully or partially hydrogenated pure monomer resins, fully or partially hydrogenated C5 / alicyclic resins, fully or partially hydrogenated C5 / alicyclic / styrene / C9 resins, fully or partially hydrogenated alicyclic resins, and combinations thereof.

5. The process according to claim 1, wherein the additional polymer is selected from the group consisting of PE homopolymer, PE copolymer, MDPE, HDPE, LLDPE, LDPE, PP homopolymer, PP copolymer, ethylene-octene copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, ethylene-acrylate copolymer, ethylene ethyl acrylate copolymer, ethylene methyl acrylate copolymer, ethylene butyl acrylate copolymer, and terpolymers of ethylene, ethyl acrylate and maleic anhydride.

6. The process according to claim 1, wherein A, B, and C are brought into contact without complete mixing or by dry blending before being added to the melt blending process.

7. The process according to claim 1, wherein the process imparts a specific energy of about 0.01 to about 10 kWh / kg to the polyolefin composition during the molten blend.

8. The process according to claim 1, wherein the melt blend is performed using a single-screw extruder, a co-rotating twin-screw extruder, a counter-rotating twin-screw extruder, or a combination thereof.

9. The process according to claim 1, wherein the melt blend is produced using a co-rotating twin-screw extruder having a screw temperature profile of about 110 to about 200°C for polyethylene-rich recycled polyolefins and about 140 to about 220°C for polypropylene-rich recycled polyolefins.

10. The process according to claim 1, wherein the random alpha-olefin copolymer (B), the tackifier (C), or a combination of both (B+C) is added to one or more masterbatches, the final random alpha-olefin copolymer (B) and / or tackifier (C) concentration is achieved by combining recycled polyolefin with the masterbatches, and the masterbatches are brought into contact without complete mixing or by dry blending before being added to the melt blending process.

11. The process according to claim 1, wherein the masterbatch is prepared using a carrier polymer which may be the same as or different from the recycled polyolefin (A) and which may be the same as or different from the optional additional polymer (D), and the carrier polymer has an MFR of about 0.5 to about 25 g / 10 min.

12. The process according to claim 1, wherein the percentage of the random alpha-olefin copolymer (B), the tackifier (C), or a combination of both (B+C) in the masterbatch is about 5 to about 70%.

13. The process according to claim 1, wherein the masterbatch is produced by melt-blending the carrier polymer with at least one random alpha-olefin copolymer and / or tackifier.

14. The process according to claim 1, wherein the melt blend of the masterbatch is carried out using a co-rotating twin-screw extruder having a screw temperature profile of about 85 to about 160°C for polyethylene carrier polymers and about 120 to about 185°C for polypropylene carrier polymers.

15. The process according to claim 11, wherein the masterbatch further comprises at least one additive and / or one or more fillers.

16. The process according to claim 1, wherein the masterbatch is in the form of pellets, powder, flakes, or a combination thereof, and the pellets, granules, powder, or flakes are optionally coated or sprinkled with polyethylene wax, polypropylene wax, talc, or silica to improve processability.

17. The process according to claim 1, wherein the polyolefin composition further comprises one or more additives.

18. The process according to claim 1, wherein the polyolefin composition further comprises one or more fillers.

19. The process according to claim 1, wherein the at least one random alpha-olefin copolymer (B) has a glass transition temperature of -10°C or lower (ASTM D 3418-15), the at least one tackifier (C) has a glass transition temperature of 25°C or higher (ASTM D 3418-15), and the polyolefin composition maintains acceptable mechanical properties compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier.

20. The process according to claim 1, wherein the recycled polyolefin (A) is polyethylene-rich, the at least one random alpha-olefin copolymer (B) has a glass transition temperature of -10°C or lower (ASTM D 3418-15), the at least one tackifier (C) has a glass transition temperature of 25°C or higher (ASTM D 3418-15), the polyolefin composition has an increase of about 5 to about 590% in yield elongation or break elongation compared to the same polyolefin composition without the random alpha-olefin copolymer and tackifier, and the polyolefin composition maintains acceptable mechanical properties.